Lithium-ion secondary battery
By adopting the positive electrode active material with a pseudo-spinel type crystal structure, the problem of reduced capacity and poor circulation performance of lithium-ion secondary batteries during circulation is solved, high capacity and excellent circulation performance are achieved, and the safety of the battery is improved.
Patent Information
- Application Number
- JP2023004853
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-04-05
- Filing Date
- 2023-01-17
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2038-06-25
AI Technical Summary
The existing lithium-ion secondary batteries have reduced capacity and poor circulation performance during the charging and discharging cycle, and are prone to overdischarge and safety hazards when charging for a long time with high voltage.
A positive electrode active material with a pseudo-spinel type crystal structure is used. This material is prepared by mixing the composite oxide of lithium, transition metal and oxide with sources such as chloride and fluoride and heating, so as to control the changes in the crystal structure to improve the cycle stability of the battery.
The high capacity and excellent charging and discharging cycle performance of lithium-ion secondary batteries are achieved, reducing the risk of overdischarge during long-term charging of high voltages and improving the safety and reliability of the battery.
Smart Images

Figure 0007655687000008 
Figure 0007655687000009 
Figure 0007655687000010
Abstract
Description
[Technical field]
[0001] One aspect of the present invention relates to an article, a method, or a manufacturing method. Alternatively, the present invention relates to a process, Pertaining to a machine, manufacture, or composition of matter. One embodiment of the present invention is a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, or an electronic In particular, the present invention relates to a positive electrode active material that can be used in a secondary battery. The present invention relates to a secondary battery and an electronic device having a secondary battery.
[0002] In this specification, the term "electricity storage device" refers to elements and devices having an electricity storage function in general. For example, lithium ion secondary batteries and other storage batteries (also called secondary batteries) These include lithium ion capacitors and electric double layer capacitors.
[0003] In addition, in this specification, the term "electronic device" refers to any device having a power storage device. Electro-optical devices having a power storage device, and information terminal devices having a power storage device are all electronic devices. [Background technology]
[0004] In recent years, various types of storage devices such as lithium-ion secondary batteries, lithium-ion capacitors, and air batteries have become available. The development of lithium-ion batteries, which have high power and high energy density, is particularly Secondary batteries are used in mobile phones, smartphones, tablets, and notebook computers. Portable information terminals, portable music players, digital cameras, medical equipment, next-generation clean energy - Automobiles (Hybrid Vehicles (HEV), Electric Vehicles (EV), Plug-in Hybrid Vehicles) Demand for rechargeable vehicles (PHEVs, etc.) is expanding rapidly along with the development of the semiconductor industry. As a source of energy, it has become indispensable in today's information society.
[0005] The characteristics required for lithium-ion secondary batteries are higher energy density, These include improved cycle characteristics, safety in various operating environments, and improved long-term reliability.
[0006] Therefore, we developed a positive electrode active material with the aim of improving the cycle characteristics and increasing the capacity of lithium-ion secondary batteries. Improvements to the material have been studied (Patent Document 1 and Patent Document 2). Research on the structure is also being conducted (Non-Patent Documents 1 to 3).
[0007] X-ray diffraction (XRD) is one of the techniques used to analyze the crystal structure of positive electrode active materials. ICSD (Inorganic Crystal Structure) introduced in Patent Document 5 By using the "Cture Database", it is possible to analyze XRD data. can. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2002-216760 A [Patent Document 2] JP 2006-261132 A [Non-patent literature]
[0009] [Non-Patent Document 1] Toyoki Okumura et al, “Correlation of lithium ion distribution and X-ray absorption near-edge structure in O3-and O2-lithium cobalt oxides from first-principle calculation”, Journal of Materials Chemistry, 2012, 22, p.17340-17348 [Non-Patent Document 2] Motohashi, T. et al, “Electronic phase diagram of the layered cobalt oxide system LixCoO2 (0.0≦x≦1.0)”, Physical Review B, 80(16);165114 [Non-Patent Document 3] Zhaohui Chen et al, “Staging Phase Transitions in LixCoO2”, Journal of The Electrochemical Society, 2002, 149(12) A1604-A1609 [Non-Patent Document 4] WE Counts et al, Journal of the American Ceramic Society,(1953) 36 [1] 12-17. Fig.01471 [Non-Patent Document 5] Belsky, A. et al., “New developments in the Inorganic Crystal Structure Database (ICSD): accessibility in support of materials research and design”, Acta Cryst., (2002) B58 364-369. Summary of the Invention [Problem to be solved by the invention]
[0010] One aspect of the present invention is a positive electrode for a lithium ion secondary battery having a high capacity and excellent charge / discharge cycle characteristics. It is an object of the present invention to provide an electrode active material and a method for manufacturing the same. Another object of the present invention is to provide a method for manufacturing a positive electrode active material. When used in lithium-ion secondary batteries, the capacity loss during charge / discharge cycles is suppressed. Another object of the present invention is to provide a positive electrode active material. Another object of the present invention is to provide a battery having excellent charge-discharge characteristics. One of the objectives is to provide a secondary battery that can hold a high-voltage charged state for a long period of time. The objective of the present invention is to provide a positive electrode active material in which the elution of transition metals such as cobalt is suppressed even when the positive electrode is heated. Another embodiment of the present invention is to provide a secondary battery that is safe or highly reliable. One of the challenges we face is to:
[0011] Another embodiment of the present invention is a novel substance, active material particles, a power storage device, or a manufacturing method thereof. One of the objectives is to provide the following.
[0012] The description of these problems does not preclude the existence of other problems. It is not necessary for the embodiment to solve all of these problems. It is possible to extract problems other than those mentioned above from the description of the claim. [Means for solving the problem]
[0013] In order to achieve the above object, a positive electrode active material according to one embodiment of the present invention has a The characteristic of this is that the crystal structure changes little. For example, when discharged, the crystal structure is layered rock salt type. When charged at a high voltage of about 4.6 V, it has a pseudo-spinel crystal structure. The positive electrode active material has a smaller change in crystal structure and volume before and after charging and discharging than known positive electrode active materials. There are few.
[0014] In order to prepare a positive electrode active material having a pseudo-spinel type crystal structure in the charged state, lithium After synthesizing the composite oxide particles containing ammonium, a transition metal, and oxygen, a fluorine source and a salt are added. Add a halogen source such as a halogen source and a magnesium source, mix them, and then subject them to a suitable temperature and time. It is preferable to heat the mixture at .
[0015] Halogens and magnesium are impurities in the layered rock-salt crystal structure. First, by synthesizing composite oxide particles with few impurities, a layered rock-salt type crystal structure with few defects was formed. The material may include a halogen source such as a fluorine source or a chlorine source, and By adding a magnesium source and heating at an appropriate temperature and time, it is possible to obtain a highly dense and highly porous composite with few defects. In this way, a positive electrode active material having a pseudospinel type crystal structure in an electrically charged state can be produced.
[0016] One aspect of the present invention is a method for producing a first mixture comprising mixing a lithium source, a fluorine source, and a magnesium source. A process for producing a composite oxide having lithium, a transition metal, and oxygen, and a first mixing the mixture with the second mixture to form a second mixture; and heating the second mixture. The present invention relates to a method for producing a positive electrode active material having the above structure.
[0017] In the above, the composite oxide containing lithium, a transition metal, and oxygen can be glow discharged. When analyzed by electrochemical mass spectrometry, the concentration of elements other than lithium, transition metals, and oxygen was 500 It is preferably 0 ppm wt or less.
[0018] In the above, the first mixture contains lithium fluoride L as a lithium source and a fluorine source. It is preferred to have iF.
[0019] In the above, magnesium fluoride (MgF2) was used as the fluorine source and magnesium source. The molar ratio of lithium fluoride (LiF) and magnesium fluoride (MgF2) is LiF:MgF It is preferable that 2=x:1 (0.1≦x≦0.5).
[0020] In the above, the second mixture has lithium, a transition metal, and oxygen. The transition metal TM contained in the composite oxide and the magnesium Mg contained in the first mixture Mix1 M ix1 The atomic ratio of TM to Mg is Mix1 = 1:y (0.001≦y≦0.01) It is preferable that
[0021] In the above, the heating temperature in the step of heating the second mixture is 600° C. or higher and 95° C. or lower. It is preferable that the temperature is 0°C or lower.
[0022] In the above, the heating time in the step of heating the second mixture is 2 hours or more. It is more preferable that the time is 60 hours or more.
[0023] Another aspect of the present invention is a method for manufacturing a battery using a positive electrode having a positive electrode active material produced by the above method and a negative electrode. It is a secondary battery having a Effect of the Invention
[0024] According to one embodiment of the present invention, a lithium ion secondary battery having high capacity and excellent charge / discharge cycle characteristics is provided. In addition, the present invention provides a method for producing a positive electrode active material with good productivity. It is also possible to provide a method for producing the material. In this way, it is possible to provide a positive electrode active material that suppresses the decrease in capacity during charge-discharge cycles. In addition, a high-capacity secondary battery can be provided. In addition, even if the battery is charged at a high voltage for a long period of time, the cobalt It is possible to provide a positive electrode active material in which the elution of transition metals such as ZnO, Fe, and FeNb is suppressed. It is possible to provide a highly reliable secondary battery. The present invention provides a method for manufacturing the same. [Brief description of the drawings]
[0025] [Figure 1] 1A to 1C illustrate an example of a method for manufacturing a positive electrode active material of one embodiment of the present invention. [Diagram 2] 4A to 4C illustrate another example of a method for manufacturing a positive electrode active material of one embodiment of the present invention. [Diagram 3] 1A and 1B are diagrams illustrating the charge depth and the crystal structure of a positive electrode active material of one embodiment of the present invention. [Figure 4] 1A and 1B are diagrams illustrating the charge depth and crystal structure of a conventional positive electrode active material. [Diagram 5] XRD pattern calculated from crystal structure. [Figure 6] 1A to 1C are diagrams illustrating a crystal structure and magnetic property of a positive electrode active material of one embodiment of the present invention. [Figure 7] 1A and 1B are diagrams illustrating the crystal structure and magnetism of a conventional positive electrode active material. [Figure 8] FIG. 13 is a cross-sectional view of an active material layer in the case where a graphene compound is used as a conductive assistant. [Figure 9] FIG. 4 is a diagram illustrating a method of charging a secondary battery. [Figure 10] FIG. 4 is a diagram illustrating a method of charging a secondary battery. [Figure 11]5A to 5C are diagrams illustrating a method of discharging a secondary battery. [Figure 12] FIG. 2 is a diagram illustrating a coin-type secondary battery. [Figure 13] FIG. 2 is a diagram illustrating a cylindrical secondary battery. [Figure 14] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 15] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 16] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 17] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 18] FIG. 1 is a diagram illustrating a laminated secondary battery. [Figure 19] FIG. 1 is a diagram illustrating a laminated secondary battery. [Figure 20] FIG. 2 is a diagram showing the appearance of a secondary battery. [Figure 21] FIG. 2 is a diagram showing the appearance of a secondary battery. [Figure 22] 1A to 1C are diagrams illustrating a method for manufacturing a secondary battery. [Figure 23] 1A and 1B are diagrams illustrating a bendable secondary battery. [Figure 24] 1A and 1B are diagrams illustrating a bendable secondary battery. [Diagram 25] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 26] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 27] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 28] FIG. 1 is a diagram illustrating an example of a vehicle. [Figure 29] 4 is a graph of particle size distribution of LiF, MgF2, and the first mixture of Example 1. [Diagram 30] 1A to 1C are a graph of an XPS analysis of the positive electrode active material of Example 1 and a diagram illustrating particles. [Diagram 31] 1 is a graph of an XPS analysis of the positive electrode active material of Example 1. [Diagram 32] 1 is an SEM image of the positive electrode active material of Example 1. [Diagram 33] 1 is an XRD pattern of the positive electrode active material of Example 1. [Diagram 34]1 is an XRD pattern of the positive electrode active material of Example 1. [Diagram 35] 1 is an XRD pattern of the positive electrode active material of Example 1. [Diagram 36] 1 is an XRD pattern of the positive electrode active material of Example 1. [Figure 37] 1 is an XRD pattern of the positive electrode active material of Example 1. [Figure 38] Cycle characteristics of a secondary battery using the positive electrode active material of Example 1. [Figure 39] Cycle characteristics of a secondary battery using the positive electrode active material of Example 1. [Diagram 40] Cycle characteristics of a secondary battery using the positive electrode active material of Example 1. [Diagram 41] Cycle characteristics of a secondary battery using the positive electrode active material of Example 1. [Diagram 42] 4 shows the rate characteristics of a secondary battery using the positive electrode active material of Example 1. [Diagram 43] 4 shows the rate characteristics of a secondary battery using the positive electrode active material of Example 1. [Diagram 44] 1 is a graph showing the charge capacity and voltage of Sample 1 and Sample 15 in Example 1. [Diagram 45] Graph of dQ / dV vs. V for Sample 1 and Sample 15 in Example 1. [Figure 46] 1 is a graph of dQ / dV vs. V for Sample 1 in Example 1. [Figure 47] 1 is a graph of dQ / dV vs. V for Sample 1 in Example 1. [Figure 48] 1 is a graph showing the discharge capacity and voltage of Sample 1 and Sample 4 in Example 1. [Figure 49] 1 is a graph showing dQ / dV vs. V of Sample 1 and Sample 4 in Example 1. [Figure 50] XRD patterns of Sample 21 and Sample 22 in Example 2. [Figure 51] XRD patterns of Sample 21 and Sample 22 in Example 2. [Figure 52] XRD patterns of Sample 23 and Sample 24 in Example 2. [Figure 53] XRD patterns of Sample 25 and Sample 26 in Example 2. [Figure 54] Charge / discharge cycle characteristics. [Figure 55] DSC evaluation results. [Figure 56] XRD patterns. [Figure 57] XRD patterns. [Figure 58] Charge / discharge cycle characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. The present invention is not limited to the following description, and various modifications in form and details are possible by those skilled in the art. The present invention is not limited to the description of the following embodiments. It is not something that can be done.
[0027] In this specification, crystal planes and directions are indicated by Miller indices. In the above, in crystallography, the numbers are usually surrounded by superscript bars. Instead of putting a bar above the number, a minus sign (-) may be placed before the number. Also, individual orientations that indicate directions within a crystal are indicated by [ ], and a collective orientation that indicates all equivalent directions is indicated by < >, individual faces that indicate crystal faces are ( ), and collective faces with equivalent symmetry are {}. Express it.
[0028] In this specification, segregation refers to a solid consisting of multiple elements (e.g., A, B, C). This refers to the phenomenon in which a certain element (e.g. B) is distributed spatially non-uniformly.
[0029] In this specification, the surface layer of a particle of an active material or the like refers to a region extending from the surface to about 10 nm. The surface caused by cracks or fractures can also be called the surface. It's called inside.
[0030] In the present specification and the like, the layered rock-salt type crystal structure of a composite oxide containing lithium and a transition metal is The structure has a rock-salt type ion arrangement in which cations and anions are arranged alternately, and the transition metal and lithium The lithium atoms are regularly arranged to form a two-dimensional plane, allowing two-dimensional diffusion of lithium. The term refers to a crystal structure. It is acceptable for there to be defects such as deficiencies of cations or anions. Strictly speaking, the rock salt crystal structure is a distorted structure of the rock salt crystal lattice. be.
[0031] In the present specification and the like, the rock salt type crystal structure refers to a structure in which cations and anions are arranged alternately. The structure may contain a deficiency of cations or anions.
[0032] In the present specification and the like, the pseudospinel type of a composite oxide containing lithium and a transition metal is The crystal structure is in the space group R-3m, and is not a spinel type crystal structure, but it does contain cobalt, The ions such as magnesium ions occupy the 6-coordinated oxygen sites, and the arrangement of cations is similar to that of the spinel type. The pseudo-spinel type crystal structure is characterized by the fact that it is difficult to separate light elements such as lithium from the crystal structure. may occupy the 4-coordinate oxygen site, and in this case the ionic arrangement also has a symmetrical structure similar to that of the spinel type. It has sexuality.
[0033] The pseudospinel crystal structure has random Li between the layers, but the CdCl2 crystal structure It can be said that the crystal structure is similar to that of the CdCl2 type. The structure is that when lithium nickel oxide is charged to a charge depth of 0.94 (Li 0.06 NiO 2) It has a similar crystal structure to pure lithium cobalt oxide, or a layered rock containing a large amount of cobalt. It is known that salt-type positive electrode active materials do not usually have this crystal structure.
[0034] Layered rock salt crystals and the anions of rock salt crystals have a cubic close-packed structure (face-centered cubic lattice structure) It is assumed that the anions of pseudospinel crystals also have a cubic close-packed structure. When the anions are in contact with each other, there exists a crystal plane where the cubic close-packed structure formed by the anions is oriented in the same direction. However, the space group of the layered rock salt crystals and pseudospinel crystals is R-3m, and the space group of the rock salt crystals is R-3m. Crystal space groups Fm-3m (the common rock salt crystal space group) and Fd-3m (the simplest Since the space group of the crystal is different from that of the rock salt type crystals, the mirror of the crystal plane that satisfies the above conditions The -index is different between layered rock salt crystals and pseudospinel crystals and between rock salt crystals. In layered rock salt crystals, pseudospinel crystals, and rock salt crystals, the anions form When the orientation of the cubic close-packed structure is aligned, the crystal orientation is roughly the same. be.
[0035] The crystal orientation of the two regions roughly coincides, as can be seen from TEM (transmission electron microscope) and STEM images. (Scanning Transmission Electron Microscope) Image, HAADF-STEM (High Angle Scattering Annular Dark Field Scanning Transmission Electron Microscope) This can be judged from images such as ABF-STEM (annular bright-field scanning transmission electron microscope) images. X-ray diffraction (XRD), electron diffraction, neutron diffraction, etc. can also be used for judgment. In TEM images, the arrangement of cations and anions is observed as repeated bright and dark lines. When the orientation of the cubic close-packed structure in the layered rock salt crystal and the rock salt crystal is aligned, the intercrystalline The angle between the repeated bright and dark lines is 5 degrees or less, and preferably 2.5 degrees or less. In addition, light elements such as oxygen and fluorine can be clearly observed in TEM images. In some cases, this is not possible, but in that case, the alignment of the metal elements can be used to determine the alignment. .
[0036] In this specification, the theoretical capacity of the positive electrode active material refers to the capacity of the positive electrode active material that can be inserted and removed. The theoretical capacity of LiCoO2 is 274 mAh / g, the theoretical capacity of LiNiO2 is 274mAh / g, and the theoretical capacity of LiMn2O4 is It is 148mAh / g.
[0037] In the present specification, the charge depth when all the intercalable and detachable lithium is intercalated is The charge depth when all the intercalable lithium in the positive electrode active material is deintercalated is defined as 0, and the charge depth when all the intercalable lithium in the positive electrode active material is deintercalated is defined as 1. That is what I will say.
[0038] In this specification, charging refers to transferring lithium ions from the positive electrode to the negative electrode in a battery. The positive electrode active material is a material that moves electrons from the negative electrode to the positive electrode in an external circuit. In this case, charging refers to the process of releasing lithium ions. .9 or less, more specifically, a positive electrode active material with a charge depth of 0.8 to 0.83 is charged at a high voltage. For example, in LiCoO2, 219. If it is charged at 2mAh / g, it is a positive electrode active material charged at a high voltage. In 2, in a 25°C environment, the charging voltage is 4.525V to 4.65V (counter electrode lithium After that, the current is 0.01C, or the voltage during constant current charging is The positive electrode active material after constant voltage charging until the current value is about 1 / 5 to 1 / 100 of the original value is also This is referred to as a charged positive electrode active material.
[0039] Similarly, discharging means moving lithium ions from the negative electrode to the positive electrode in the battery and discharging them from an external circuit. The term refers to the transfer of electrons from the positive electrode to the negative electrode in a battery. The insertion of ions is called discharging. Also, the positive electrode active material with a charge depth of 0.06 or less, or The positive electrode active material that has been discharged from a high-voltage charged state to 90% or more of its charge capacity is then For example, the charge capacity of LiCoO2 is 21 If the battery is charged at 9.2mAh / g, it is in a high-voltage charged state, and from this point, it is at 90% of its charge capacity. The positive electrode active material after discharging 197.3 mAh / g or more is considered to be a fully discharged positive electrode active material. In addition, in the case of LiCoO2, the battery voltage is 3V or less (counter electrode lithium) in a 25°C environment. The positive electrode active material after constant current discharge until the positive electrode That is what I will say.
[0040] In this specification, a non-equilibrium phase change refers to a phenomenon that causes a non-linear change in a physical quantity. For example, the capacitance (Q) is differentiated by the voltage (V) to obtain d A non-equilibrium phase change occurs before and after the peak in the Q / dV curve, and the crystal structure changes significantly. It is believed that this is the case.
[0041] (Embodiment 1) [Method of producing positive electrode active material] First, an example of a method for producing a positive electrode active material 100 according to an embodiment of the present invention will be described with reference to FIG. Another specific example of the manufacturing method is shown in FIG.
[0042] <Step S11> As shown in step S11 of FIG. 1, first, a fluorine source or a chlorine source is used as a material for the first mixture. A halogen source such as fluorine or fluorine-containing fluorine and a magnesium source are prepared. It is also preferable to prepare a lithium source. It is nice.
[0043] As the fluorine source, for example, lithium fluoride, magnesium fluoride, etc. can be used. Among them, lithium fluoride has a relatively low melting point of 848°C, and it melts in the annealing process described below. The chlorine source is preferably lithium chloride, magnesium chloride, etc. The magnesium source can be, for example, magnesium fluoride, magnesium oxide, etc. The lithium source can be, for example, sodium, magnesium hydroxide, magnesium carbonate, etc. For example, lithium fluoride and lithium carbonate can be used. Magnesium fluoride can be used as both a lithium source and a fluorine source. Umium can be used as both a fluorine source and a magnesium source.
[0044] In this embodiment, lithium fluoride (LiF) is prepared as the fluorine source and the lithium source. Magnesium fluoride (MgF2) will be prepared as a fluorine source and magnesium source. Step S11 in FIG. 2. Lithium fluoride LiF and magnesium fluoride MgF2 are Mixing F:MgF2 at a molar ratio of about 65:35 will have the greatest effect in lowering the melting point. On the other hand, if the amount of lithium fluoride is too large, the lithium becomes excessive and the cyclopentadiene becomes unstable. Therefore, lithium fluoride (LiF) and magnesium fluoride (MgF) are The molar ratio of MgF2 is preferably LiF:MgF2=x:1 (0≦x≦1.9). More preferably, LiF:MgF2=x:1 (0.1≦x≦0.5) is used. 2=x:1 (x=near 0.33) is more preferable. The value shall be greater than 0.9 times but less than 1.1 times that value.
[0045] If the subsequent mixing and grinding steps are to be carried out in a wet manner, a solvent is prepared. ketones such as toluene, alcohols such as ethanol and isopropanol, ethers, San, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is more preferable to use an aprotic solvent which is less likely to react with lithium. In this embodiment, acetone is used (see step S11 in FIG. 2).
[0046] <Step S12> Next, the materials of the first mixture are mixed and pulverized (step S1 in FIG. 1 and FIG. 2). 2) Mixing can be done either dry or wet, but wet mixing allows for smaller particles to be ground. For mixing, a ball mill, a bead mill, etc. can be used. When using a ball mill, it is preferable to use, for example, zirconia balls as the media. It is preferable to carry out this mixing and grinding step sufficiently to pulverize the first mixture into fine particles.
[0047] <Step S13, Step S14> The mixed and crushed materials are collected (step S13 in FIG. 1 and FIG. 2), and the first mixture is (Step S14 in FIG. 1 and FIG. 2).
[0048] The first mixture may have an average particle diameter (D50: also called median diameter) of 600 nm or less. It is preferable that the thickness is 20 μm or less, and more preferable that the thickness is 1 μm or more and 10 μm or less. If the first mixture is thus finely powdered, lithium, transition metals and When mixed with the oxygen-containing composite oxide, the first mixture is uniformly distributed on the surface of the composite oxide particles. When the first mixture is uniformly adhered to the surface of the composite oxide particles, After heating, halogen and magnesium are easily distributed throughout the surface layer of the composite oxide particles. If there is an area on the surface layer that does not contain halogen or magnesium, charging In this state, it may be difficult to obtain a pseudospinel crystal structure, which will be described later.
[0049] <Step S21> Next, as shown in step S21 of FIG. 1, a composite having lithium, a transition metal, and oxygen is formed. As the oxide material, a lithium source and a transition metal source are prepared.
[0050] As the lithium source, for example, lithium carbonate, lithium fluoride, etc. can be used.
[0051] The transition metal may be at least one of cobalt, manganese, and nickel. The composite oxides containing lithium, transition metals, and oxygen have a layered rock-salt type crystal structure. Therefore, the mixture ratio of cobalt, manganese, and nickel that can form a layered rock salt structure is In addition, it is preferable to use these transition metals within a range in which a layered rock salt type crystal structure can be formed. Aluminum may also be added.
[0052] As the transition metal source, oxides, hydroxides, etc. of the above transition metals can be used. Examples of the manganese source that can be used include cobalt oxide and cobalt hydroxide. As the nickel source, manganese oxide, manganese hydroxide, etc. can be used. As the aluminum source, nickel oxide, nickel hydroxide, etc. can be used. Aluminum oxide, aluminum hydroxide, etc. can be used.
[0053] <Step S22> Next, the lithium source and the transition metal source are mixed (step S22 in FIG. 1). Mixing can be carried out in a dry or wet manner. For example, a ball mill, a bead mill, etc. are used for mixing. When using a ball mill, for example, zirconia balls are used as the media. It is preferable that
[0054] <Step S23> Next, the mixed material is heated. This process is called "sintering" to distinguish it from the subsequent heating process. The heating is preferably performed at a temperature of 800° C. or higher and lower than 1100° C. It is preferable to carry out the treatment at a temperature of 900°C or higher and 1000°C or lower, and more preferably about 950°C or higher. If the temperature is too low, the starting materials may not be sufficiently decomposed and melted. On the other hand, if the temperature is too high, the transition metals may be excessively reduced, or lithium may evaporate. Defects may occur. For example, defects in which cobalt becomes divalent may occur.
[0055] The heating time is preferably from 2 hours to 20 hours. This can be done in an atmosphere with low dew point (for example, below -50°C, more preferably below -100°C). For example, heating is performed at 1000°C for 10 hours, the temperature is increased by 200°C / h, and the mixture is heated in a dry atmosphere. The flow rate of the ambient air is preferably 10 L / min. The heated material is then cooled to room temperature. For example, the time required for cooling from a specified temperature to room temperature can be set to 10 hours or more and 50 hours or less. It is preferable to set the above.
[0056] However, cooling to room temperature in step S23 is not essential. 4. There is no problem in carrying out the steps S25 and S31 to S34. If desired, cooling may be to a temperature above room temperature.
[0057] <Step S24, Step S25> The calcined material is collected (step S24 in FIG. 1), and lithium, transition metals, and oxygen are separated. A composite oxide having the following structure is obtained (Step S25 in FIG. 1). Specifically, lithium cobalt oxide , lithium manganese oxide, lithium nickel oxide, cobalt oxide in which some of the cobalt is replaced by manganese Lithium baltic oxide, or lithium nickel-manganese-cobalt oxide, is obtained.
[0058] In step S25, a catalyst having lithium, a transition metal, and oxygen that has been synthesized in advance is prepared. In this case, steps S21 to S22 may be used. The 4 can be omitted.
[0059] When a composite oxide having lithium, a transition metal, and oxygen that has been synthesized in advance is used, It is preferable to use a material with few impurities. The composite oxide containing lithium and oxygen, and the positive electrode active material mainly composed of lithium, cobalt, and nickel Nickel, manganese, aluminum and oxygen, with elements other than the above main components as impurities. For example, when analyzed by glow discharge mass spectrometry, the total impurity concentration was 10,000ppm. It is preferably m wt or less, and more preferably 5000 ppm wt or less. The total impurity concentration of transition metals such as titanium and arsenic is 3000 ppm wt or less. It is preferable that the content of the EDTA be 1500 ppm by weight or less, and more preferable that the content of the EDTA be 1500 ppm by weight or less.
[0060] For example, lithium cobalt oxide (LiCO3) manufactured by Nippon Chemical Industry Co., Ltd. is used as a pre-synthesized lithium cobalt oxide. Lithium barium oxide particles (product name: Cellseed C-10N) can be used. The average particle size (D50) is approximately 12 μm, and the measured value by glow discharge mass spectrometry (GD-MS) is In the impurity analysis, the magnesium and fluorine concentrations were 50 ppm or less by weight, and calcium Sium, aluminum and silicon concentrations are 100 ppm or less by weight, nickel Concentration is 150 ppm wt or less, sulfur concentration is 500 ppm wt or less, and arsenic concentration is 110 0 ppm wt or less, other elements other than lithium, cobalt and oxygen are 150 ppm pm wt or less, lithium cobalt oxide.
[0061] Or, lithium cobalt oxide particles (product name: Cellseed C-5) manufactured by Nippon Chemical Industry Co., Ltd. H) can also be used. This has an average particle size (D50) of about 6.5 μm and is GD- In the MS impurity analysis, the concentration of elements other than lithium, cobalt, and oxygen was C-1 It is lithium cobalt oxide, which is about the same as or lower than 0N.
[0062] In this embodiment, cobalt is used as the transition metal, and a lithium cobalt oxide that has been synthesized in advance is used. The tungsten particles (Cellseed C-10N manufactured by Nippon Chemical Industry Co., Ltd.) were used (Figure 2 reference).
[0063] The composite oxide having lithium, a transition metal and oxygen in step S25 is formed by forming defects and strain. It is preferable that the crystal structure of the layered rock salt type has few impurities. It is preferable that the oxide is a composite oxide having lithium, a transition metal, and oxygen. If there are many of these, the crystal structure is likely to be defective or distorted.
[0064] <Step S31> Next, the first mixture is mixed with a composite oxide having lithium, a transition metal, and oxygen. (Step S31 in FIG. 1 and FIG. 2). The transition metal TM in the first mixture Mix1 and the magnesium Mg Mix1 Nohara The molecular ratio is TM:Mg Mix1 = 1:y (0.0005 ≦ y ≦ 0.03) TM:Mg Mix1 = 1:y (0.001 ≦ y ≦ 0.01) is more preferable. TM:Mg Mix1 A ratio of about 1:0.005 is even more preferable.
[0065] The mixing in step S31 is carried out more slowly than the mixing in step S12 in order not to destroy the composite oxide particles. For example, the rotation speed is set to be milder than that of the mixing in step S12. It is preferable to use conditions with less heat or shorter time. Also, the dry method is gentler than the wet method. For example, a ball mill, a bead mill, etc. can be used for mixing. When using a ball mill, for example, zirconia balls can be used as the media. preferable.
[0066] <Step S32, Step S33> The mixed material is collected (step S32 in FIG. 1 and FIG. 2) to obtain a second mixture. (Step S33 in Figures 1 and 2).
[0067] In this embodiment, the mixture of lithium fluoride and magnesium fluoride is The present invention relates to a method of adding a small amount of lithium cobalt oxide to the Instead of the second mixture in step S33, a starting material of lithium cobalt oxide may be used. Alternatively, a magnesium source and a fluorine source may be added to the material and then calcined. Steps S11 to S14 and steps S21 to S25 Since there is no need to separate the steps, this method is simple and highly productive.
[0068] Alternatively, lithium cobalt oxide predoped with magnesium and fluorine was used. Magnesium and fluorine doped lithium cobalt oxide is also suitable. This makes it easier to omit the steps up to S32.
[0069] In addition, lithium cobalt oxide, to which magnesium and fluorine had been added in advance, was A magnesium source and a fluorine source may be added to the above.
[0070] <Step S34> Next, the second mixture is heated. This step is also called annealing to distinguish it from the previous heating step. This is sometimes called second heating.
[0071] The annealing is preferably carried out at a suitable temperature and time. Particle size and structure of composite oxides containing lithium, transition metals, and oxygen in Step S25 It depends on the composition and other conditions. Small particles can be heated at a lower temperature or in a shorter time than large particles. A shorter time may be more preferable.
[0072] For example, when the average particle diameter (D50) of the particles in step S25 is about 12 μm, the annealing temperature The annealing temperature is preferably, for example, 600° C. or higher and 950° C. or lower. The annealing time is preferably, for example, 3 hours or longer. It is preferably 10 hours or more, more preferably 60 hours or more.
[0073] On the other hand, when the average particle diameter (D50) of the particles in step S25 is about 5 μm, the annealing temperature The annealing temperature is preferably, for example, 600° C. or higher and 950° C. or lower. The annealing time is, for example, 1 hour to 10 hours. Preferably, the time is less than 1 hour, and more preferably, about 2 hours.
[0074] The temperature drop time after annealing is preferably, for example, 10 hours or more and 50 hours or less.
[0075] When the second mixture is annealed, the material with a lower melting point (e.g., fluoride) in the first mixture is first melted. It is believed that lithium (melting point 848°C) melts and distributes in the surface layer of the composite oxide particles. The presence of this molten material then causes the melting point of other materials to drop, causing them to melt. For example, magnesium fluoride (melting point 1263℃) melts and turns into composite oxide particles. It is thought to be distributed on the surface of the fetus.
[0076] The elements contained in the first mixture distributed in the surface layer are lithium, transition metals, and oxygen. It is believed that the Cr content is dissolved in the complex oxide having the Cr content.
[0077] The diffusion of the elements contained in the first mixture is more pronounced in the surface layer and the grains than in the interior of the composite oxide particles. Therefore, magnesium and halogens are more likely to dissolve in the surface layer and near the grain boundaries. As will be described later, the magnesium concentration in the surface layer and near the grain boundaries is When the temperature is high, the change in the crystal structure can be more effectively suppressed.
[0078] <Step S35> The annealed material described above is recovered to obtain the positive electrode active material 100 according to one embodiment of the present invention.
[0079] When fabricated using the methods shown in Figures 1 and 2, pseudo-spindles with few defects are formed when charged at high voltage. It is possible to produce a positive electrode active material with a spinel-type crystal structure. Positive electrode active materials with a crystalline structure of 50% or more have excellent cycle and rate characteristics. It is an active material.
[0080] In order to prepare a positive electrode active material having a pseudo-spinel crystal structure after high-voltage charging, the positive electrode active material It is made by containing magnesium and fluorine and annealing at the appropriate temperature and time. It is effective to prepare the composite oxide by adding a magnesium source and a fluorine source to the starting material. However, when added to the starting material of the composite oxide, the magnesium source and the fluorine If the melting point of the fluorine source is higher than the firing temperature, the magnesium source and the fluorine source do not melt and diffusion is difficult. This can lead to many defects or distortions in the layered rock salt crystal structure. Therefore, the pseudospinel crystal structure after high-voltage charging also has defects or Distortion may occur.
[0081] Therefore, first of all, we developed a layered rock-salt type crystal structure with few impurities and few defects or distortion. It is preferable to obtain a composite oxide having a magnesium source in the subsequent step. and a fluorine source are mixed and annealed to form magnesium and fluorine in the surface layer of the composite oxide. By producing the material in this manner, defects or It is possible to prepare a positive electrode active material having a pseudospinel structure with little distortion.
[0082] In addition, the positive electrode active material 100 produced in the above process may be further coated with another material. Further heating may be carried out.
[0083] For example, the positive electrode active material 100 can be mixed with a compound containing phosphoric acid. By mixing a compound containing phosphoric acid, it can be heated at high voltage. The positive electrode activity suppresses the elution of transition metals such as cobalt even when the battery is kept in a charged state for a long period of time. By heating after mixing, phosphoric acid can be more uniformly coated. It can be overturned.
[0084] Examples of compounds containing phosphoric acid include lithium phosphate and ammonium dihydrogen phosphate. The mixing can be carried out, for example, by a solid phase method. The heating can be carried out, for example, at 800°C. This can be done for up to 2 hours.
[0085] [Positive electrode active material structure] Next, referring to FIG. 3 and FIG. 4, a positive electrode according to one embodiment of the present invention that can be produced by the above method will be described. The active material 100 and a conventional positive electrode active material will be described, and the differences between them will be described. FIG. 4 illustrates the case where cobalt is used as the transition metal in the positive electrode active material. The conventional positive electrode active material described in Figure 4 contains elements other than lithium, cobalt, and oxygen. It is a simple cobalt alloy that has not been processed by adding cobalt to the surface or coating the surface. Lithium trioxide (LiCoO2).
[0086] <Conventional positive electrode active materials> Lithium cobalt oxide LiCoO2, one of the conventional positive electrode active materials, is described in Non-Patent Document 1 and Non-Patent Document 2. As described in Reference 2, the crystal structure changes depending on the charge depth. A typical crystal structure of lithium is shown in Figure 4.
[0087] As shown in FIG. 4, lithium cobalt oxide at a charge depth of 0 (discharged state) is in the space group R-3. m crystal structure, and there are three CoO2 layers in the unit cell. This crystal structure is sometimes called the O3 type crystal structure. This refers to a structure in which an octahedral structure in which oxygen is coordinated six times is connected in a plane with edge sharing.
[0088] At a charge depth of 1, the crystal structure has the space group P-3m1, and there is CoO There is one 2-layer structure. Therefore, this crystal structure is sometimes called the O1-type crystal structure.
[0089] In addition, when the charge depth is about 0.88, lithium cobalt oxide has a crystal structure of the space group R-3m. This structure is similar to the structure of CoO2, such as P-3m1(O1), and R-3m(O3 ) and the structure of LiCoO2, which is layered alternately. The crystal structure is sometimes called the H1-3 crystal structure. , the number of cobalt atoms per unit cell is twice that of the other structures. In this specification, the c-axis of the H1-3 crystal structure is united to facilitate comparison with other structures. The figure will be shown as half the size of a cell.
[0090] Repeated high voltage charging and discharging until the charge depth reaches 0.88 or more. Lithium cobalt oxide has a H1-3 crystal structure and a discharged R-3m(O3) structure. The crystal structure changes (i.e., non-equilibrium phase change) between these two states repeatedly.
[0091] However, these two crystal structures have a large misalignment of the CoO2 layers. As shown by the arrows in the figure, in the H1-3 crystal structure, the CoO2 layer is significantly separated from the R-3m(O3) layer. Such dynamic structural changes adversely affect the stability of the crystal structure. Ugh.
[0092] Furthermore, the difference in volume is also large. When comparing per the same number of cobalt atoms, the H1-3 crystal structure The difference in volume between the O3-type crystal structure and the discharged state is more than 3.5%.
[0093] In addition, the H1-3 type crystal structure has continuous CoO2 layers like P-3m1(O1). The resulting structure is likely to be unstable.
[0094] Therefore, the crystal structure of lithium cobalt oxide breaks down when it is repeatedly charged and discharged at high voltages. The breakdown of the crystal structure causes the deterioration of cycle characteristics. The number of sites where lithium can exist stably decreases, and it becomes difficult to insert and remove lithium. It is believed that this is the case.
[0095] <Positive Electrode Active Material of One Embodiment of the Present Invention> ≪Inside≫ In contrast, the positive electrode active material 100 of one embodiment of the present invention has a sufficiently discharged state and a high voltage The change in the crystal structure and the number of transition metal atoms per unit charge were compared. The difference in volume is small in this case.
[0096] The crystal structure of the positive electrode active material 100 before and after charging and discharging is shown in FIG. It is a composite oxide having cobalt and oxygen. In addition to the above, it also has magnesium. It is also preferable that the compound contains a halogen atom such as fluorine or chlorine.
[0097] The crystal structure at charge depth 0 (discharged state) in Figure 3 is the same as that in Figure 4, R-3m(O3). In the case of the positive electrode active material 100 according to one embodiment of the present invention, when the charge depth is sufficiently 0.88, 4. The crystal structure of this space group R-3m is referred to herein as The pseudo-spinel crystal structure shown in FIG. In the structure diagram, the lithium ions are used to explain the symmetry of the cobalt atoms and the symmetry of the oxygen atoms. The number of atoms is omitted, but in reality, there is about 12 atomic % of cobalt between the CoO2 layers. Lithium is present. In both the O3 and pseudospinel crystal structures, In this case, magnesium is preferably present in a dilute state between the CoO2 layers, i.e., at the lithium sites. In addition, it is known that halogens such as fluorine are present randomly and dilutely at oxygen sites. preferable.
[0098] In the positive electrode active material 100, when a large amount of lithium is released by charging at a high voltage, the crystal structure changes. For example, as shown by the dotted line in Figure 3, In these crystal structures, there is almost no misalignment of the CoO2 layers.
[0099] In addition, the positive electrode active material 100 has an O3 type crystal structure at a charge depth of 0 and a pseudo-sintered structure at a charge depth of 0.88. The difference in volume per unit cell of the Pinel crystal structure is 2.5% or less, more specifically, 2.2 % or less.
[0100] Therefore, the crystal structure is not easily destroyed even when repeatedly charged and discharged at high voltage.
[0101] In addition, the pseudospinel crystal structure has the coordinates of cobalt and oxygen in the unit cell as Co(0 ,0,0.5), O(0,0,x), 0.20≦x≦0.25. do.
[0102] Magnesium, which exists randomly and dilutely between the CoO2 layers, i.e., on the lithium sites, is This has the effect of suppressing the shift of the oO2 layers. Therefore, magnesium exists between the CoO2 layers. Therefore, magnesium is easily formed into a pseudo-spinel crystal structure. It is preferable that magnesium is distributed throughout the particles. In the process of producing the positive electrode active material 100, a heat treatment is preferably performed.
[0103] However, if the heat treatment temperature is too high, cation mixing occurs and the magnesium The possibility of magnesium entering the cobalt site increases. When magnesium is present in the cobalt site, The effect of maintaining the structure of R-3m will be lost. Furthermore, if the heat treatment temperature is too high, There are also concerns about adverse effects such as cobalt being reduced to divalent and lithium evaporating. do.
[0104] Therefore, prior to the heat treatment to distribute magnesium throughout the particles, the lithium cobaltate was It is preferable to add a halogen compound such as a fluorine compound to the lithium. The addition of lithium cobalt oxide lowers the melting point of the lithium cobalt oxide. At a temperature where unmixing is unlikely to occur, it becomes easy to distribute magnesium throughout the particles. Furthermore, if fluorine compounds are present, the electrolyte will have high corrosion resistance against hydrofluoric acid produced by decomposition. It can be expected to improve.
[0105] In the past, the positive electrode active material 100 was a composite oxide having lithium, cobalt, and oxygen. In the above description, the alloy may contain nickel in addition to cobalt. In the case of , the number of nickel atoms in the sum of the number of cobalt and nickel atoms (Co + Ni) is The ratio of Ni / (Co+Ni) is preferably less than 0.1, and more preferably 0.075 or more. It is more preferable that it is below.
[0106] If the battery is charged at a high voltage for a long period of time, transition metals will dissolve from the positive electrode active material into the electrolyte. However, by having nickel in the above ratio, the positive electrode active material In some cases, it may be possible to suppress the leaching of transition metals from the material 100.
[0107] By adding nickel, the charge / discharge voltage is reduced, so for the same capacity, the voltage is reduced. This may result in suppressing the elution of transition metals and the decomposition of the electrolyte. The charge / discharge voltage here refers to, for example, a voltage in the range from a charge depth of zero to a predetermined charge depth.
[0108] ≪Surface layer≫ It is preferable that magnesium is distributed throughout the particles of the positive electrode active material 100. In addition, it is more preferable that the magnesium concentration in the surface layer of the particle is higher than the average concentration in the whole particle. In other words, the magnesium concentration in the particle surface layer measured by XPS etc. is different from that measured by ICP-MS etc. It is more preferable that the magnesium concentration is higher than the average magnesium concentration of the whole particle. If this happens, it is all due to crystal defects, and when charging, lithium is removed from the surface, so This is the area where the lithium concentration is likely to be lower than that of the other areas. Therefore, the crystal structure is easily unstable. If the magnesium concentration in the surface layer is high, the crystal structure will change more easily. In addition, if the magnesium concentration in the surface layer is high, the electrolyte decomposes. It is also expected that the corrosion resistance against the hydrofluoric acid produced by the process will be improved.
[0109] In addition, the concentration of halogens such as fluorine in the surface layer of the positive electrode active material 100 is higher than the average concentration of the whole particle. The presence of halogen in the surface layer, which is the region in contact with the electrolyte, The corrosion resistance against fluoric acid can be effectively improved.
[0110] In this way, the surface layer of the positive electrode active material 100 has a higher concentration of magnesium and fluorine than the inside. It is preferable that the composition of the inner layer is different from that of the inner layer. Therefore, the surface layer may have a different crystal structure from the interior. For example, at least a part of the surface layer of the positive electrode active material 100 has a rock salt type crystal structure. In addition, when the surface layer and the inside have different crystal structures, the crystal orientation of the surface layer and the inside may be different. It is preferable that these values are approximately equal.
[0111] However, if the surface layer is made of only MgO or a solid solution of MgO and CoO(II), Therefore, the surface layer must contain at least cobalt, In the discharged state, it must also contain lithium and have a path for lithium insertion and removal. Also, a higher concentration of cobalt than magnesium is preferred.
[0112] ≪Grain boundary≫ The magnesium or halogen contained in the positive electrode active material 100 is present randomly and dilutely inside. However, it is more preferable that a part of them is segregated at the grain boundaries.
[0113] In other words, the magnesium concentration at and near the grain boundaries of the positive electrode active material 100 is also It is preferable that the halogen concentration at the grain boundary and its vicinity is higher than that in other regions. It is preferable that the thickness of the slab is higher than that of other regions.
[0114] Like the particle surface, the grain boundary is also a planar defect. Therefore, it is prone to instability and changes in the crystal structure. Therefore, if the magnesium concentration is high at and near the grain boundaries, The change in the crystal structure can be more effectively suppressed.
[0115] In addition, when the magnesium and halogen concentrations at and near the grain boundaries are high, the positive electrode active material Even if a crack occurs along the grain boundary of a grain with a quality of 100, the surface area caused by the crack The magnesium and halogen concentrations are high near the surface. The corrosion resistance of the positive electrode active material to hydrofluoric acid can also be improved.
[0116] In this specification, the vicinity of the grain boundary refers to the region within about 10 nm from the grain boundary. It is decided.
[0117] ≪Particle size≫ If the particle size of the positive electrode active material 100 is too large, it becomes difficult for lithium to diffuse. On the other hand, if the size is too small, the surface of the active material layer becomes too rough. There are also problems such as the active material layer becoming difficult to support when applied to the body and excessive reaction with the electrolyte. Therefore, D50 is preferably 1 μm or more and 100 μm or less, and more preferably 2 μm or more and 40 μm or less. It is more preferable that the thickness is 5 μm or less, and further preferably 5 μm or more and 30 μm or less.
[0118] <Analysis method> An embodiment of the present invention in which a certain positive electrode active material exhibits a pseudospinel crystal structure when charged at a high voltage. Whether or not the positive electrode active material 100 is the positive electrode active material 100 is determined by subjecting the positive electrode charged at a high voltage to XRD, electron beam diffraction, Analysis using neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc. In particular, XRD can be used to determine the symmetry of the transition metals, such as cobalt, contained in the positive electrode active material. It is possible to analyze with high resolution, compare the crystallinity and crystal orientation, and measure the periodic distortion of the lattice. The crystallite size can also be analyzed by measuring the positive electrode obtained by disassembling the secondary battery. This is preferable in that sufficient accuracy can be obtained.
[0119] As described above, the positive electrode active material 100 according to one embodiment of the present invention has a high voltage charging state and a discharged state. The characteristic of this battery is that the crystal structure changes little when it is charged or discharged. Materials with a crystal structure that exhibits large changes in state and temperature, accounting for 50 wt% or more, can withstand high-voltage charging and discharging. Furthermore, the desired crystal structure cannot be achieved by simply adding impurity elements. It should be noted that there are cases where the magnesium and cobalt with fluorine are Although they have in common the fact that they are both lithium tungsten oxides, they have a pseudo-spinel crystal structure when charged at high voltages. When the H1-3 crystal structure accounts for 50 wt% or more, At a certain voltage, the pseudo-spinel crystal structure is almost 100 wt %. If the voltage is increased to the specified level, the H1-3 crystal structure may be generated. In order to determine whether the positive electrode active material 100 of the present embodiment is a positive electrode active material 100, the crystal structure of the positive electrode active material 100 can be determined by XRD or other methods. Analysis of the structure is required.
[0120] However, the positive electrode active material in a charged or discharged state at high voltage loses its crystal structure when exposed to air. For example, the pseudo-spinel crystal structure may change to the H1-3 crystal structure. Therefore, all samples should be handled in an inert atmosphere such as argon. Ringing is preferred.
[0121] ≪Charging method≫ A high-temperature method for determining whether a certain composite oxide is the positive electrode active material 100 of one embodiment of the present invention Voltage charging is done by using a coin cell (CR2032 type, diameter 20 mm height) with lithium as the counter electrode. 3.2mm) can be created and charged.
[0122] More specifically, the positive electrode is formed by mixing a positive electrode active material, a conductive additive, and a binder in a slurry. Alternatively, a positive electrode current collector made of aluminum foil may be coated with the conductive material.
[0123] The counter electrode can be made of lithium metal. However, if a material other than lithium metal is used for the counter electrode, When the secondary battery is in a charged state, the potential of the secondary battery is different from the potential of the positive electrode. Unless otherwise specified, the potential is that of the positive electrode.
[0124] The electrolyte used in the electrolytic solution is 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte contains ethylene carbonate (EC) and diethyl carbonate (DEC). C:DEC=3:7 (volume ratio), vinylene carbonate (VC) was mixed at 2 wt%. can be used.
[0125] The separator can be made of polypropylene having a thickness of 25 μm.
[0126] The positive and negative electrode cans may be made of stainless steel (SUS). do.
[0127] The coin cell prepared under the above conditions was charged at a constant current of 4.6 V and 0.5 C, and the current value was Charge at a constant voltage until the temperature reaches 0.01C. Here, 1C is 137mA / g. Temperature After charging in this way, the coin cell was placed in a globe with an argon atmosphere. If you disassemble it in the box and take out the positive electrode, you can obtain the positive electrode active material charged with high voltage. When performing various analyses after the experiment, the container is sealed in an argon atmosphere to prevent reactions with external components. For example, XRD can be performed in a sealed container with an argon atmosphere. Cut.
[0128] <XRD> The CuKα1 line calculated from the pseudo-spinel crystal structure and the H1-3 crystal structure model. The ideal powder XRD pattern obtained by this is shown in Figure 5. For comparison, the LiCoO 2(O3) and the ideal XRD calculated from the crystal structure of CoO2(O1) at charge depth 1 The patterns of LiCoO2(O3) and CoO2(O1) are also shown. SD (Inorganic Crystal Structure Database) (See Non-Patent Document 5) Reflex Powder Diffr, one of the modules of (BIOVIA) The 2θ range was from 15° to 75°, and the step size was e=0.01, wavelength λ1=1.540562×10 -10 m, λ2 is not set, Mono The chromator was set to single. The H1-3 crystal structure pattern was taken from the non-patent literature. The pseudospinel pattern was similarly created from the crystal structure information described in 3 of the present invention. The crystal structure was estimated from the XRD pattern of the positive electrode active material and analyzed using TOPAS ver.3 (Bruk The XRD patterns were fitted using the crystal structure analysis software (E.K. Electron Crystallography). We created a new version of the program.
[0129] As shown in Figure 5, in the pseudospinel crystal structure, 2θ = 19.30 ± 0.20° (19. 10° to 19.50°), and 2θ=45.55±0.10° (45.45° or less) A diffraction peak appears at 2θ=19.30° (45.65° or less). ±0.10° (19.20° to 19.40°) and 2θ=45.55±0.0 A sharp diffraction peak appears at 5° (45.50° or more and 45.60° or less). No peaks appear at these positions in the type crystal structure and CoO2 (P-3m1, O1). Therefore, when charged at high voltage, 2θ=19.30±0.20° and 2θ=4 The appearance of the peak at 5.55±0.10° indicates that the positive electrode active material 100 according to one embodiment of the present invention It can be said to be a characteristic.
[0130] This is the crystal structure at 0 charge depth and the crystal structure when charged at high voltage, and the diffraction peaks of XRD More specifically, the positions of the main diffraction peaks of both are close to each other. The difference in the positions at which the peaks appear in two or more of the above, more preferably three or more of the above, is 2θ= It can be said that the angle is 0.7 or less, and more preferably 2θ=0.5 or less.
[0131] The positive electrode active material 100 according to one embodiment of the present invention has a pseudo-spinel crystal structure when charged at a high voltage. However, not all of the particles need to have a pseudo-spinel type crystal structure. However, the XRD pattern may be When the rhottveld analysis was performed, it was found that the pseudo-spinel crystal structure was preferably 50 wt% or more. It is preferable that the content of the cellulose ester is 60 wt% or more, more preferably 66 wt% or more. It is preferable that the pseudo-spinel crystal structure is 50 wt% or more, more preferably 60 wt% or more, and further preferably If the content is preferably 66 wt % or more, the positive electrode active material has sufficiently excellent cycle characteristics. can be done.
[0132] In addition, even after more than 100 charge / discharge cycles from the start of the measurements, Rietveld analysis showed that The pseudo-spinel crystal structure is preferably 35 wt% or more, more preferably 40 wt% or more. It is more preferable that the content is 43 wt % or more, and further more preferable that the content is 43 wt % or more.
[0133] In addition, the crystallite size of the pseudo-spinel structure of the positive electrode active material particles is The XR of the positive electrode before and after charging and discharging is the same as that of the positive electrode before and after charging and discharging. Even under the measurement conditions of D, a clear peak of the pseudospinel crystal structure was observed after high-voltage charging. On the other hand, in simple LiCoO2, some of the structures resembled pseudospinel crystal structures. Even if the crystallite size is small, the peak becomes broad and small. , can be determined from the half-width of the XRD peak.
[0134] In addition, the layered rock-salt structure of the particles of the positive electrode active material in the discharged state, which can be estimated from the XRD pattern, In the crystal structure, it is preferable that the lattice constant of the c-axis is small. When a foreign element is substituted at the Zn site, or when cobalt enters the oxygen tetracoordination site (A site), etc. Therefore, first of all, there is little Co3O4 with a foreign element substitution and spinel type crystal structure. In other words, a complex oxide with a layered rock-salt type crystal structure with few defects is created, and then magnesium The magnesium was inserted into the lithium site by mixing the sodium and fluorine sources. It is believed that it is possible to produce a positive electrode active material that exhibits cycling characteristics.
[0135] The c-axis lattice constant in the crystal structure of the positive electrode active material in the discharged state is 14.060 before annealing. ×10 -10 m or less is preferable, and 14.055×10 -10 m or less is more preferable, and 14 .051×10 -10 m or less is more preferable. The lattice constant of the c-axis after annealing is 14. 060×10 -10 m or less is preferable.
[0136] In order to keep the c-axis lattice constant in the above range, it is preferable to have a small amount of impurities, especially cobalt. The amount of transition metals other than manganese and nickel added is preferably small. It is preferable that the content is 0 ppm or less, and more preferable that the content is 1500 ppm or less. It is also preferable that the cation mixing between lithium and cobalt, manganese, or nickel is small. It is preferable to do so.
[0137] The characteristics revealed from the XRD pattern are characteristics of the internal structure of the positive electrode active material. In the case of positive electrode active materials with an average particle diameter (D50) of about 1 μm to 100 μm, the In comparison, the volume of the surface layer is very small, so the surface layer of the positive electrode active material 100 is different from the inside. Even if the material has a crystal structure similar to that of the crystalline material, it is highly likely that this will not show up in the XRD pattern.
[0138] <ESR> Here, the difference between the pseudo-spinel crystal structure and other crystal structures will be described with reference to Figs. 6 and 7. The case of using ESR to make this judgment is explained below. For the pseudo-spinel crystal structure, see Fig. 3 and As shown in Figure 6(A), cobalt exists in the site with 6 oxygen coordination. In the case of cobalt with 6 oxygen coordination, the 3d orbitals are e g Orbit and t 2g split into orbits, where oxygen is present t, which is an orbit that avoids the direction 2g Low orbital energy. Oxygen 6-coordinated site The part of the cobalt that 2g Diamagnetic Co with all orbitals filled 3+ The most common is cobalt. However, the other part of the cobalt present in the oxygen 6-coordinated sites is paramagnetic Co 2+ Or Co 4 + The paramagnetic cobalt may be Co 2+ and Co 4+ In either case Since there is only one unpaired electron in the nucleus, they cannot be distinguished by ESR. However, the valence of the surrounding elements determines the Therefore, either valence may be taken.
[0139] On the other hand, conventional positive electrode active materials are spinel-type batteries that do not contain lithium in the surface layer when charged. In this case, the spinel shown in FIG. The resulting material has a Co3O4 crystal structure.
[0140] When describing spinel with the general formula A[B2]O4, element A has 4 oxygen coordination and element B has 6 oxygen coordination. Therefore, in this specification, the site with 4 oxygen coordination is called the A site, and the site with 6 oxygen coordination is called the B site. The site is sometimes called the B site.
[0141] In the spinel-type crystal structure of Co3O4, not only the B site with 6 oxygen atoms but also the B site with 4 oxygen atoms Cobalt is also present at the A site. As shown in Figure 7(B), in the case of cobalt with 4 oxygen coordination, Split e g Orbit and t 2g Of the orbitals, e g The orbital energy is low. Therefore, the oxygen 4- Co 2+ , Co 3+ and Co 4+ All of them have unpaired electrons and are paramagnetic. Therefore, if a particle having sufficient spinel-type Co3O4 is analyzed by ESR etc., it is found that the Co 2+ , Co 3+ Or Co 4+ A peak due to paramagnetic cobalt should be detected. do.
[0142] However, in the positive electrode active material 100 according to one embodiment of the present invention, the oxygen-coordinated paramagnetic cobalt is Therefore, the pseudospinel referred to in this specification and the like is Unlike spinel, it does not contain any ESR-detectable amounts of cobalt with four oxygen coordinates. Therefore, compared to the conventional example, the positive electrode active material of one embodiment of the present invention has a higher spin that can be detected by ESR or the like. The peaks due to the Co3O4 nanoparticles may be small or too few to be recognized. Since spinel type Co3O4 does not contribute to the charge / discharge reaction, the less spinel type Co3O4, the better. As seen from the ESR analysis, the positive electrode active material 100 is different from the conventional examples. It can be determined that:
[0143] <XPS> X-ray photoelectron spectroscopy (XPS) measures the surface to a depth of about 2 to 8 nm (usually about 5 nm). Since it is possible to analyze the area, the concentration of each element can be quantified for about half of the surface layer. In addition, narrow scan analysis can be used to analyze the bonding state of elements. The quantitative accuracy of XPS is usually about ±1 atomic %, and the detection limit depends on the element. It depends on the material, but is about 1 atomic percent.
[0144] When XPS analysis was performed on 100% positive electrode active material, the cobalt concentration was set to 1. The relative value of the magnesium concentration is preferably 0.4 or more and 1.5 or less, and more preferably 0.45 or more and less than 1.00. The relative value of the concentration of halogen such as fluorine is preferably 0.05 or more and 1.5 or less. It is preferable that the ratio is 0.3 or more and 1.00 or less.
[0145] In addition, when the positive electrode active material 100 was analyzed by XPS, the bond energy between fluorine and other elements was The peak showing the ion exchange reaction is preferably 682 eV or more and less than 685 eV, and more preferably 684.3 eV. It is more preferable that the bond energy of the bond is about 68 5 eV, and the binding energy of magnesium fluoride, 686 eV. In other words, when the positive electrode active material 100 contains fluorine, lithium fluoride and Bonds other than magnesium fluoride are preferred.
[0146] Furthermore, when the positive electrode active material 100 was analyzed by XPS, the bonds between magnesium and other elements were The peak showing the energy is preferably 1302 eV or more and less than 1304 eV, It is more preferable that the bond energy of magnesium fluoride is about 1303 eV. This value is different from the 1305 eV, which is the energy of magnesium oxide. In other words, when the positive electrode active material 100 contains magnesium, magnesium fluoride A bond other than the following is preferred.
[0147] <EDX> Among EDX measurements, ED is a method of measuring an area while scanning it and evaluating the area in two dimensions. Also, data on linear areas is extracted from EDX area analysis, and the original Evaluation of the distribution of the molecular concentration within the positive electrode active material particles is sometimes called line analysis.
[0148] EDX surface analysis (e.g. elemental mapping) was used to identify the internal, surface and grain boundary regions. The concentrations of magnesium and fluorine can be quantitatively analyzed. The analysis allows for peaks in magnesium and fluorine concentrations to be determined.
[0149] When EDX analysis was performed on the positive electrode active material 100, the peak of magnesium concentration in the surface layer It is preferable that the surface of the positive electrode active material 100 is located at a depth of up to 3 nm toward the center. Preferably, the surface is present at a depth of 1 nm, and more preferably at a depth of 0.5 nm. is more preferred.
[0150] In addition, the distribution of fluorine in the positive electrode active material 100 preferably overlaps with the distribution of magnesium. Therefore, when EDX analysis is performed, the peak of the fluorine concentration in the surface layer is It is preferable that the surface of the 100 is located within a depth of 3 nm toward the center, and the depth of 1 nm More preferably, it is present to a depth of 0.5 nm. stomach.
[0151] In addition, when the positive electrode active material 100 was subjected to line analysis or area analysis, the microstructure in the vicinity of the grain boundaries was The ratio of the number of magnesium and cobalt atoms (Mg / Co) is preferably 0.020 or more and 0.50 or less. It is more preferable that the ratio is 0.025 or more and 0.30 or less. It is even more preferable that the ratio is 0.030 or more and 0. 20 or less is preferable.
[0152] ≪dQ / dVvsV curve≫ In addition, the positive electrode active material of one embodiment of the present invention can be charged at a low voltage, for example, at 0.2 C or less. When discharging at a certain rate, a characteristic voltage change may appear near the end of the discharge. In the dQ / dV vs V curve obtained from the discharge curve, the range is 3.5V to 3.9V. , which can be clearly seen by the presence of at least one peak.
[0153] (Embodiment 2) In this embodiment, a secondary battery having the positive electrode active material 100 described in the previous embodiment is used. In this embodiment, the positive electrode, the negative electrode, and the electrolyte are Here, a secondary battery enclosed in an exterior body will be taken as an example.
[0154] [Positive electrode] The positive electrode has a positive electrode active material layer and a positive electrode current collector.
[0155] <Cathode active material layer> The positive electrode active material layer includes at least a positive electrode active material. In addition, other substances such as a coating on the surface of the active material, a conductive aid, or a binder may be included.
[0156] As the positive electrode active material, the positive electrode active material 100 described in the previous embodiment can be used. By using the positive electrode active material 100 described in the previous embodiment, it is possible to obtain a high capacity and good cycle characteristics. This makes it possible to produce an excellent secondary battery.
[0157] As the conductive assistant, a carbon material, a metal material, a conductive ceramic material, or the like can be used. In addition, a fibrous material may be used as the conductive assistant. The content of the electrical auxiliary agent is preferably 1 wt% or more and 10 wt% or less, and more preferably 1 wt% or more and 5 wt% or less. is more preferred.
[0158] The conductive assistant can form an electrical conductive network in the active material layer. The conductive agent can maintain the electrical conduction path between the positive electrode active materials. By adding an electrical auxiliary agent, it is possible to realize an active material layer having high electrical conductivity. .
[0159] Examples of the conductive assistant include natural graphite, artificial graphite such as mesocarbon microbeads, and carbon fibers. Examples of carbon fibers that can be used include mesophase pitch carbon fibers. In addition, carbon fibers such as isotropic pitch-based carbon fibers can be used. Carbon nanofibers and carbon nanotubes can be used. The tube can be produced by, for example, a vapor phase growth method. For example, carbon black (acetylene black (AB) etc.), graphite particles Carbon materials such as copper, nickel, and graphene can be used. Nickel, aluminum, silver, gold and other metal powders, metal fibers, conductive ceramic materials, etc. It can be used.
[0160] In addition, a graphene compound may be used as the conductive assistant.
[0161] Graphene compounds have excellent electrical properties, such as high electrical conductivity, as well as high flexibility and In addition, graphene may have excellent physical properties such as high mechanical strength. The compound has a planar shape. Graphene compounds enable surface contact with low contact resistance. In addition, even if the material is thin, it can have very high conductivity, and a small amount of the material can be used to efficiently conduct electricity within the active material layer. Therefore, the graphene compound can be used as a conductive additive. This is preferable because it is possible to increase the contact area between the active material and the conductive assistant. By using a laser dryer, the entire surface of the active material is covered with graphene, which is a conductive additive. It is preferable to form the compound as a coating. In addition, electrical resistance may be reduced. Here, examples of the graphene compound include graphene, multigraphene, It is particularly preferred to use RGO, where RGO is, for example, graphene oxide (g This refers to a compound obtained by reducing raphene oxide (GO).
[0162] When using an active material with a small particle size, for example, an active material with a particle size of 1 μm or less, the specific surface area of the active material is Therefore, a large amount of conductive additive is required. This tends to result in a relatively reduced amount of active material carried. If the capacity of the secondary battery decreases, the capacity of the secondary battery decreases. When graphene compounds are used, they efficiently form conductive paths even in small amounts. This is particularly preferable because it is possible to avoid reducing the amount of the active material carried.
[0163] In the following, as an example, a graphene compound is used as a conductive assistant in the active material layer 200. An example of the cross-sectional structure will be described.
[0164] 8A shows a vertical cross-sectional view of the active material layer 200. The active material layer 200 is made of granular positive electrode active material. 100, a graphene compound 201 as a conductive assistant, and a binder (not shown). Here, the graphene compound 201 may be, for example, graphene or multi-graphene. Here, the graphene compound 201 preferably has a sheet shape. In addition, the graphene compound 201 may include a plurality of multi-graphenes or (and) a plurality of The graphene may be partially overlapped to form a sheet.
[0165] In the vertical cross section of the active material layer 200, as shown in FIG. 8(B), In FIG. 8(B), the sheet-like graphene compound 201 is dispersed almost uniformly. The graphene compound 201 is shown in bold in schematic form, but in reality it is a single or multiple layer of carbon molecules. The graphene compounds 201 are thin films having a thickness of 100 nm. The positive electrode active material 100 is partially covered with the positive electrode active material 100 or is attached to the surface of a plurality of positive electrode active material particles 100. Since the electrodes are formed as described above, they are in surface contact with each other.
[0166] Here, a plurality of graphene compounds are bonded to each other to form a mesh-like graphene compound. The graphene compound is then bonded to the graphene sheet (hereinafter referred to as a graphene compound net or a graphene net). When the active material is covered with a graphene net, the graphene net can connect the active materials together. It can also function as a binder to bind the material together. This allows the amount of binder to be reduced. The ratio of active material to the electrode volume or weight can be adjusted to suit the application. In other words, the capacity of the secondary battery can be increased.
[0167] Here, graphene oxide is used as the graphene compound 201, and is mixed with an active material to form an active material. After the layer that will become the layer 200 is formed, it is preferable to reduce it. By using graphene oxide, which has extremely high dispersibility in polar solvents, The mixture 201 can be dispersed approximately uniformly inside the active material layer 200. The solvent is removed by evaporation from the dispersion medium containing the dispersed graphene oxide, and the graphene oxide is reduced. Therefore, the graphene compounds 201 remaining in the active material layer 200 are partially overlapped with each other. By dispersing the particles so that they are in surface contact with each other, a three-dimensional conductive path can be formed. The reduction of graphene oxide may be performed, for example, by heat treatment or by using a reducing agent. It is also possible.
[0168] Therefore, unlike granular conductive additives such as acetylene black, which come into point contact with the active material, graphite Since the compound 201 enables surface contact with low contact resistance, it is more effective than ordinary conductive additives. The amount of the positive electrode active material 100 and the graphene compound 201 is reduced, and the electrical conductivity between the positive electrode active material 100 and the graphene compound 201 is improved. Therefore, the ratio of the positive electrode active material 100 in the active material layer 200 can be increased. This makes it possible to increase the discharge capacity of the secondary battery.
[0169] In addition, the entire surface of the active material is covered with a conductive additive in advance using a spray dryer. A graphene compound is formed as a coating, and the active material is then conductively bonded to the graphene compound. An electrical path can also be formed.
[0170] Examples of binders include styrene-butadiene rubber (SBR) and styrene-isoprene. Acrylonitrile-styrene rubber, butadiene rubber, ethylene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, It is preferable to use a rubber material such as a propylene-diene copolymer. Fluorine rubber can be used.
[0171] As the binder, it is preferable to use, for example, a water-soluble polymer. As the molecule, for example, polysaccharides can be used. CMC, methyl cellulose, ethyl cellulose, hydroxypropyl cellulose Cellulose derivatives such as cellulose, diacetyl cellulose, regenerated cellulose, and starch These water-soluble polymers can be used in combination with the above-mentioned rubber materials. It is even better if there is a
[0172] Alternatively, the binder may be polystyrene, polymethyl acrylate, or polymethyl methacrylate. (Polymethylmethacrylate, PMMA), Sodium polyacrylate, Polyvinyl Alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, Polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene Polyisobutylene, Polyethylene terephthalate, Nylon, Polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, It is preferable to use materials such as polyvinyl acetate and nitrocellulose.
[0173] The binder may be used in combination of two or more of the above.
[0174] For example, a material having a particularly excellent viscosity adjusting effect may be used in combination with other materials. For example, rubber materials have excellent adhesive strength and elasticity, but it is difficult to adjust the viscosity when mixed with a solvent. In such cases, for example, it is possible to mix the material with a particularly excellent viscosity adjusting effect. As a material having a particularly excellent viscosity adjusting effect, for example, a water-soluble polymer is preferably used. In addition, examples of water-soluble polymers that are particularly effective in adjusting viscosity include the aforementioned polysaccharides, such as calcium carbonate. Carboxymethylcellulose (CMC), methylcellulose, ethylcellulose, hydroxy Cellulose derivatives such as propyl cellulose, diacetyl cellulose, and regenerated cellulose For example, starch or starch can be used.
[0175] In addition, cellulose derivatives such as carboxymethyl cellulose are, for example, carboxymethyl The solubility of cellulose increases when it is converted into a salt such as sodium salt or ammonium salt. It is easy to exert its effect as a viscosity adjuster. The higher the solubility, the easier it is to make the electrode slurry. In the preparation of the electrode, the dispersibility of the electrode with the active material and other components can be improved. In this regard, the cellulose and cellulose derivatives used as the binder for the electrodes are as follows: These salts are also included.
[0176] Water-soluble polymers stabilize the viscosity by dissolving in water, and also serve as active materials and binders. Other materials to be combined, such as styrene butadiene rubber, are stable in aqueous solution. In addition, since it has a functional group, it is easy to stably adsorb on the surface of the active material. It is expected that cellulose derivatives such as carboxymethyl cellulose, for example, For example, many materials have functional groups such as hydroxyl groups and carboxyl groups. It is expected that the polymers will interact with each other and widely cover the surface of the active material.
[0177] When the binder that covers or contacts the surface of the active material forms a film, it is called a passive film. It is expected that the passive film will also play a role in preventing the decomposition of the electrolyte. A film with no electrical conductivity or extremely low electrical conductivity is used. For example, When a dynamic membrane is formed, it is possible to suppress the decomposition of the electrolyte at the battery reaction potential. In addition, the passive film suppresses electrical conductivity while allowing lithium ions to conduct. And even more desirable.
[0178] <Positive electrode current collector> The positive electrode current collector may be made of metals such as stainless steel, gold, platinum, aluminum, titanium, or the like. In addition, the material used for the positive electrode current collector can be an alloy of these materials, which has high electrical conductivity. It is preferable that the material does not dissolve at the potential of the positive electrode. Aluminum alloys containing elements such as indium and molybdenum that improve heat resistance are used. It can also be formed from a metal element that reacts with silicon to form a silicide. Metal elements that react with silicon to form silicide include zirconium, titanium, and Tantalum, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten , cobalt, nickel, etc. Current collectors are available in foil, plate (sheet), mesh, punched The current collector may be in the form of a metal, an expanded metal, or the like. It is advisable to use one with a thickness of 5 μm or more and 30 μm or less.
[0179] [Negative electrode] The negative electrode has a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer contains a conductive assistant and and a binder.
[0180] <Negative electrode active material> As the negative electrode active material, for example, an alloy-based material or a carbon-based material can be used.
[0181] As a negative electrode active material, it is possible to carry out charge / discharge reactions by alloying / de-alloying reactions with lithium. For example, silicon, tin, gallium, aluminum, and Rumanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. Materials containing at least one of these elements can be used. These elements have a large capacity compared to carbon. Silicon has a high theoretical capacity of 4200mAh / g. It is preferable to use silicon. Compounds containing these elements may also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V 2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3 Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, I nSb, SbSn, etc. Here, the charge / discharge reaction occurs due to alloying / dealloying reactions with lithium. Elements capable of undergoing a reaction and compounds containing such elements are sometimes called alloy materials. do.
[0182] In this specification, SiO refers to, for example, silicon monoxide. Alternatively, SiO x Here, it is preferable that x has a value close to 1. For example, x is 0 A value between 0.2 and 1.5 is preferred, and a value between 0.3 and 1.2 is more preferred.
[0183] Carbon-based materials include graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Carbon nanotubes, graphene, carbon black, etc. may be used. .
[0184] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include mesophase graphite. Carbon microbeads (MCMB), coke-based artificial graphite, pitch-based artificial graphite, etc. Here, as the artificial graphite, spherical graphite having a spherical shape can be used. For example, the MCMB may have a spherical shape, which is preferred. It is relatively easy to reduce the particle size, which may be preferable. Examples of the graphite include flake graphite and spherical natural graphite.
[0185] When lithium ions are inserted into graphite (the formation of lithium-graphite intercalation compounds), It shows a low potential similar to that of lithium metal (0.05V to 0.3V vs. Li / Li + This allows the lithium-ion secondary battery to exhibit a high operating voltage. In addition, graphite has a relatively high capacity per unit volume, a relatively small volume expansion, and is inexpensive. It is preferable because it has the advantage of being safer than metallic lithium.
[0186] In addition, titanium dioxide (TiO2) and lithium titanium oxide (Li4T i5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5) Oxides such as tungsten oxide (WO2) and molybdenum oxide (MoO2) can be used. can.
[0187] In addition, the negative electrode active material is a composite nitride of lithium and transition metals, which has a Li3N structure. Li 3-x M x N (M=Co, Ni, Cu) can be used. For example, Li 2.6 Co 0.4 N3 has a large charge / discharge capacity (900mAh / g, 1890mAh / cm 3 ) And preferable.
[0188] When a composite nitride of lithium and transition metals is used, the negative electrode active material contains lithium ions, The positive electrode active material is made of V2O5, Cr3O8, etc., which do not contain lithium ions. It is preferable that the positive electrode active material contains lithium ions. The lithium ions contained in the positive electrode active material are first removed to form the negative electrode active material. A complex nitride of lithium and a transition metal can be used.
[0189] In addition, a material that undergoes a conversion reaction can also be used as the negative electrode active material. For example, Lithium oxide (LiO), cobalt oxide (CoO), nickel oxide (NiO), iron oxide (FeO), etc. A transition metal oxide that does not form an alloy with the negative electrode active material may be used. Further materials that are produced include Fe2O3, CuO, Cu2O, RuO2, Cr2O3, etc. oxide, CoS 0.89 , NiS, CuS and other sulfides, Zn3N2, Cu3N, Ge3 Nitrides such as N4, phosphides such as NiP2, FeP2, CoP3, FeF3, BiF3, etc. It also occurs with fluoride.
[0190] The conductive assistant and binder that can be contained in the negative electrode active material layer are the same as those that can be contained in the positive electrode active material layer. The conductive additive and binder may be the same as those that can be used.
[0191] <Negative electrode current collector> The negative electrode current collector can be made of the same material as the positive electrode current collector. It is preferable to use a material that does not alloy with carrier ions such as lithium.
[0192] [Electrolyte] The electrolytic solution contains a solvent and an electrolyte. The solvent for the electrolytic solution is preferably an aprotic organic solvent. For example, ethylene carbonate (EC), propylene carbonate (PC), ethylene carbonate, chloroethylene carbonate, vinylene carbonate, gamma-butyrolactone lactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate ethyl propionate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1 ,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethylsulfur oxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran One of trihydrofuran, sulfolane, sultone, etc., or two or more of these Combinations and ratios may be used.
[0193] In addition, a flame-retardant and non-volatile ionic liquid (room-temperature molten salt) is used as the solvent for the electrolyte. By using one or more, the internal temperature of the secondary battery increases due to an internal short circuit or overcharging. Even if the battery is heated, it can prevent explosion or fire of the secondary battery. Ionic liquids are made of cations and anions. The electrolyte solution contains an organic cation and an anion. Ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations, etc. Aliphatic onium cations such as imidazolium cations and pyridinium cations Aromatic cations are also used as anions in electrolytes. Anions, monovalent methide anions, fluorosulfonate anions, perfluoroalkyl Sulfonate anion, tetrafluoroborate anion, perfluoroalkylborate anion, hexafluorophosphate anion, or perfluoroalkyl phosphate anions, etc.
[0194] The electrolyte to be dissolved in the above solvent is, for example, LiPF6, LiClO4, Li AsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4 , Li2B 10 Cl 10 , Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO 3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2) 2. Lithium such as LiN(C4F9SO2)(CF3SO2) and LiN(C2F5SO2)2 Use one or more of these salts in any combination and ratio. can be done.
[0195] The electrolyte used in secondary batteries is free of granular waste and elements other than the constituent elements of the electrolyte (hereinafter simply referred to as "inorganic substances"). It is preferable to use a highly purified electrolyte solution with a low content of ruthenium oxide (also called "pure substance"). Specifically, the weight ratio of impurities to the electrolyte is 1% or less, preferably 0.1% or less, more preferably It is preferably 0.01% or less.
[0196] In addition, vinylene carbonate, propane sultone (PS), and tert-butyl ether were used in the electrolyte. Benzene (TBB), Fluoroethylene carbonate (FEC), Lithium bis(oxalate) Lithium borate (LiBOB), as well as dinitriles such as succinonitrile and adiponitrile Additives such as compounds may be added. The concentration of the added material is, for example, It is sufficient to set the content to 0.1wt% or more and 5wt% or less.
[0197] Alternatively, a polymer gel electrolyte may be used in which a polymer is swollen with an electrolytic solution.
[0198] By using a polymer gel electrolyte, safety against leakage etc. is improved. It is possible to reduce the thickness and weight of the device.
[0199] The polymers that can be gelled include silicone gel, acrylic gel, acrylonitrile gel, Polyethylene oxide gel, polypropylene oxide gel, fluorine-based polymer A gel or the like can be used.
[0200] Examples of the polymer include polyalkylene oxides such as polyethylene oxide (PEO). Polymers with a fluororesin structure, PVDF, polyacrylonitrile, etc., and their combinations For example, a copolymer containing PVDF and hexafluoropropylene (H PVDF-HFP, a copolymer of PVDF and PVDF, can be used. The mer may have a porous shape.
[0201] In addition, instead of the electrolyte, solid electrolytes containing inorganic materials such as sulfides and oxides, and P A solid electrolyte containing a polymer material such as EO (polyethylene oxide) can be used. When a solid electrolyte is used, the installation of a separator or spacer becomes unnecessary. Since the entire pond can be solidified, there is no risk of leakage, and safety is improved dramatically.
[0202] [Separator] The secondary battery preferably has a separator. The separator may be, for example, a paper. , nonwoven fabric, glass fiber, ceramics, or nylon (polyamide), vinylon (poly Vinyl alcohol fiber), polyester, acrylic, polyolefin, polyurethane The separator can be made of synthetic fibers or the like. It is preferable that the separator is processed into a shape such that it envelops either the positive electrode or the negative electrode.
[0203] The separator may be a multi-layer structure. For example, the separator may be made of an organic material such as polypropylene or polyethylene. The material film is made of ceramic, fluorine, polyamide, or a mixture of these materials. The ceramic material can be, for example, aluminum oxide. Examples of the fluorine-based material include fluorine particles, silicon oxide particles, etc. PVDF, polytetrafluoroethylene, etc. can be used. For example, nylon, aramid (meta-aramid, para-aramid), etc. can be used. can.
[0204] Coating with ceramic materials improves oxidation resistance, making it ideal for separators during high-voltage charging and discharging. This suppresses the deterioration of the capacitor and improves the reliability of the secondary battery. By coating the electrode, the separator and the electrode are more easily adhered to each other, improving the output characteristics. Coating polyamide materials, especially aramid, improves heat resistance, which contributes to the safety of secondary batteries. This can improve safety.
[0205] For example, a polypropylene film is coated on both sides with a mixture of aluminum oxide and aramid. Alternatively, aluminum oxide may be applied to the surface of the polypropylene film that comes into contact with the positive electrode. Alternatively, the surface in contact with the negative electrode may be coated with a mixed material of carbon and aramid, and then coated with a fluorine-based material.
[0206] By using a multi-layered separator, the safety of the secondary battery can be ensured even if the overall thickness of the separator is thin. Since the capacity per unit volume of the secondary battery can be increased, the capacity per unit volume of the secondary battery can be increased.
[0207] [Exterior body] The exterior body of the secondary battery is made of, for example, a metal material such as aluminum or a resin material. Also, a film-like exterior body can be used. For example, polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc. On the film made of the material, a flexible metal such as aluminum, stainless steel, copper, nickel, etc. is A thin metal film is then applied, and a polyamide resin or polyester resin is applied to the outer surface of the exterior body on the thin metal film. For example, a three-layer film having an insulating synthetic resin film such as a fluorine-based resin can be used.
[0208] [Charge / discharge method] The secondary battery can be charged and discharged, for example, as follows.
[0209] ≪CC charging≫ First, we will explain CC charging, which is one of the charging methods. CC charging is This is a charging method in which a constant current is passed through the secondary battery and charging is stopped when a specified voltage is reached. Assuming that the secondary battery is an equivalent circuit with internal resistance R and secondary battery capacity C as shown in Figure 9(A), In this case, the secondary battery voltage V B is the voltage V across the internal resistance R R and the secondary battery capacity C Applied voltage V C It is the sum of.
[0210] During CC charging, as shown in Figure 9(A), the switch is turned on and a constant current is applied. Current I flows through the secondary battery. During this time, current I is constant, so V R = R × I Ohm's Law According to the law, the voltage V across the internal resistance R R On the other hand, the voltage applied to the secondary battery capacity C is constant. Pressure V C increases over time. Therefore, the secondary battery voltage V B As time passes, Both rise.
[0211] and the secondary battery voltage V B When the voltage reaches a certain value, for example 4.3V, charging is stopped. When CC charging is stopped, the switch is turned off and the current I = 0, as shown in Figure 9(B). Therefore, the voltage V applied to the internal resistance R R Therefore, the secondary battery voltage V B decreases.
[0212] The secondary battery voltage V during CC charging and after CC charging is stopped B and the charging current An example is shown in FIG. 9(C). The secondary battery voltage V B But, C C It shows a slight decrease after charging is stopped.
[0213] ≪CCCV charging≫ Next, we will explain CCCV charging, which is a charging method different from the above. First, charge the battery to a specified voltage using CC charging, then use CV (constant voltage) charging to reduce the current flowing. This is a charging method in which charging is continued until the battery becomes low, specifically until the battery reaches a cut-off current value.
[0214] During CC charging, as shown in Figure 10(A), the constant current power supply switch is on, The constant voltage power supply is switched off and a constant current I flows through the secondary battery. During this time, the current I Since is constant, V R According to Ohm's law, the voltage V across the internal resistance R is R too On the other hand, the voltage V applied to the secondary battery capacity C is constant. C increases over time. Therefore, the secondary battery voltage V B increases over time.
[0215] and the secondary battery voltage V B When the voltage reaches a certain value, for example 4.3V, the CC charge is switched to C During CV charging, the constant voltage supply is switched to constant voltage charging, as shown in Figure 10(B). The power supply switch is turned on, the constant current power supply switch is turned off, and the secondary battery voltage V B is constant On the other hand, the voltage V applied to the secondary battery capacity C C V increases over time. B =V R +V C Therefore, the voltage V across the internal resistance R R becomes smaller over time. Voltage V across internal resistance R R As becomes smaller, V R By Ohm's law, = R × I, The current I flowing through the secondary battery also becomes smaller.
[0216] When the current I flowing through the secondary battery becomes a certain current, for example, a current equivalent to 0.01C, When CCCV charging is stopped, all switches are turned off as shown in Figure 10(C). The switch is turned off and the current I becomes 0. Therefore, the voltage V across the internal resistance R R is 0V However, the voltage V applied to the internal resistance R due to CV charging R was small enough Therefore, even if the voltage drop across the internal resistance R disappears, the secondary battery voltage V B hardly descends at all.
[0217] The secondary battery voltage V during CCCV charging and after CCCV charging is stopped B And An example of the charging current is shown in Figure 10(D). Even if the CCCV charging is stopped, the secondary battery voltage V B Gahoto The figure shows that the aircraft barely descends at all.
[0218] ≪CC discharge≫ Next, we will explain CC discharge, which is one of the discharge methods. CC discharge is a method in which the A constant current flows from the secondary battery at the secondary battery voltage V B becomes a certain voltage, for example 2.5V. This is a discharge method in which the discharge is stopped when
[0219] The secondary battery voltage V during CC discharge B An example of the discharge current is shown in Fig. 11. According to the secondary battery voltage V B The figure shows how the light descends.
[0220] Next, the discharge rate and the charge rate will be described. It is the relative ratio of the current during discharge and is expressed in units of C. For a battery with a rated capacity of X (Ah), In this case, the current equivalent to 1C is X(A). When discharging with a current of 2X(A), the current is 2C. If it is discharged at a current of X / 5(A), it is said to be discharged at 0.2C. The charging rate is also the same; if you charge with a current of 2X(A), it will be charged at 2C. When the battery was charged with a current of X / 5(A), it was charged at 0.2C. .
[0221] (Embodiment 3) In this embodiment, the shape of a secondary battery having the positive electrode active material 100 described in the previous embodiment is The material used in the secondary battery described in this embodiment is the same as that in the previous embodiment. The description of the form may be taken into consideration.
[0222] [Coin-type secondary battery] First, an example of a coin-type secondary battery will be described. FIG. 12(A) shows a coin-type (single-layer flat type) 12(A) is an external view of the secondary battery shown in FIG. 12(A), and FIG. 12(B) is a cross-sectional view thereof.
[0223] The coin-type secondary battery 300 has a positive electrode can 301 that also serves as a positive electrode terminal and a negative electrode can 302 that also serves as a negative electrode terminal. 302 is insulated and sealed by a gasket 303 made of polypropylene or the like. The positive electrode 304 is composed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector 305. The negative electrode 307 is formed by contacting a negative electrode current collector 308. The negative electrode active material layer 309 is formed by bonding the negative electrode active material layer 309 to the negative electrode.
[0224] The positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 are each an active material. The barrier layer need only be formed on one side.
[0225] The positive electrode can 301 and the negative electrode can 302 are made of nickel or aluminum, which is resistant to corrosion by the electrolyte. , titanium, or alloys of these with other metals (e.g. stainless steel In addition, nickel or aluminum can be used to prevent corrosion by the electrolyte. The positive electrode can 301 is for covering the positive electrode 304, and the negative electrode can 302 is for covering the negative electrode 304. 7 and electrically connected to each other.
[0226] The negative electrode 307, the positive electrode 304, and the separator 310 are impregnated with an electrolyte, and the negative electrode 307, the positive electrode 304, and the separator 310 are impregnated with an electrolyte. As shown in FIG. 1, the positive electrode can 301 is placed downward, and the positive electrode 304, the separator 310, the negative electrode 307, The positive electrode can 301 and the negative electrode can 302 are stacked in this order, and the positive electrode can 301 and the negative electrode can 302 are secured together with a gasket 303 interposed therebetween. Then, the laminate is pressed to manufacture a coin-type secondary battery 300.
[0227] By using the positive electrode active material described in the above embodiment for the positive electrode 304, it is possible to achieve high capacity and cycle. The coin-type secondary battery 300 can be made to have excellent characteristics.
[0228] Here, the flow of current during charging of a secondary battery will be explained with reference to FIG. When a secondary battery is considered as a closed circuit, the movement of lithium ions and the flow of electric current are in the same direction. In secondary batteries that use lithium, the anode and cathode are connected by charging and discharging. The cathode (cathode) is switched, and the oxidation and reduction reactions are switched, so the reaction potential The electrode with the higher reaction potential is called the positive electrode, and the electrode with the lower reaction potential is called the negative electrode. In this case, the charge / discharge current is always the same whether the battery is charging or discharging or a reverse pulse current is applied. Even when an electric current flows through the positive electrode, it is called the "positive electrode" or "+ electrode (plus electrode)" and the negative electrode is called the "negative electrode" or "-electrode (minus electrode)". When the terms anode and cathode are used, the difference between charging and discharging is , which can lead to confusion. The term "cathode" is not used in this specification. When using the terms negative electrode ( ) or cathode ( ), specify whether they are charging or discharging, and positive electrode ( It will also be indicated whether it corresponds to a positive pole or a negative pole.
[0229] A charger is connected to the two terminals shown in FIG. 12(C) to charge the secondary battery 300. As the charging of the secondary battery 300 progresses, the potential difference between the electrodes increases.
[0230] [Cylindrical secondary battery] Next, an example of a cylindrical secondary battery will be described with reference to FIG. FIG. 13(A) shows an external view of the cylindrical secondary battery 600. FIG. 13(B) shows a schematic cross section of the cylindrical secondary battery 600. As shown in FIG. 13(B), the cylindrical secondary battery 600 has a It has a positive electrode cap (battery lid) 601 and a battery can (outer can) 602 on the side and bottom. The positive electrode cap and the battery can (outer can) 602 are connected by a gasket (insulating packing). ) 610.
[0231] Inside a hollow cylindrical battery can 602, a strip-shaped positive electrode 604 and a strip-shaped negative electrode 606 are sandwiched between a separator 6 The battery element is wound around the sensor. The battery can 602 is wound around a turbopin. One end is closed and the other end is open. The battery can 602 is made of nickel, aluminum, titanium, or other material that is resistant to corrosion by the electrolyte. The metals, or their alloys or alloys of these with other metals (e.g., stainless steel, etc.) are used. In addition, nickel, aluminum, etc. can be used as the electrode to prevent corrosion by the electrolyte. It is preferable to coat the battery can 602. On the inside of the battery can 602, the positive electrode, the negative electrode, and The battery element with the separator wound around it is sandwiched between a pair of opposing insulating plates 608 and 609. The inside of the battery can 602 in which the battery element is provided is filled with a non-aqueous electrolyte (not shown). The non-aqueous electrolyte can be the same as that used in coin-type secondary batteries. .
[0232] The positive and negative electrodes used in cylindrical storage batteries are wound, so active materials are formed on both sides of the current collector. A positive electrode terminal (positive electrode current collector lead) 603 is connected to the positive electrode 604, and a negative electrode A negative electrode terminal (negative electrode current collecting lead) 607 is connected to the positive electrode terminal 603 and the negative electrode The terminal 607 may be made of a metal material such as aluminum. 3 is resistance welded to the safety valve mechanism 612, and the negative terminal 607 is resistance welded to the bottom of the battery can 602. The safety valve mechanism 612 is a PTC (Positive Temperature Coupling) element. The positive electrode cap 601 is electrically connected to the positive electrode cap 601 via a positive electrode cap 611. When the internal pressure of the battery increases beyond a certain threshold, the valve mechanism 612 closes the positive electrode cap 601 and the The PTC element 611 cuts off the electrical connection with the positive electrode 604. This is a thermal resistance element whose resistance increases when the temperature rises. The increase in resistance limits the amount of current and prevents abnormal It prevents heat generation. The PTC element is made of barium titanate (BaTiO3) based semiconductor. Conductive ceramics or the like can be used.
[0233] 13C, a plurality of secondary batteries 600 are mounted on a conductive plate 613 and a conductive plate 614. The secondary batteries 600 may be sandwiched between the secondary batteries 600 to form a module 615. They may be connected in series or in parallel and then in series. By configuring a module 615 having a plurality of secondary batteries 600, It is possible to extract a large amount of power.
[0234] FIG. 13D is a top view of the module 615. For clarity of illustration, the conductive plate 613 is As shown in FIG. 13(D), the module 615 includes a plurality of secondary batteries 600. The device may have a conductive wire 616 for electrical connection. A conductive plate is provided on the conductive wire 616. In addition, a temperature control device 617 may be provided between the multiple secondary batteries 600. When the secondary battery 600 is overheated, the temperature control device 617 cools the secondary battery 600. If the temperature controller 617 is too cold, it can be heated. The performance of the module 615 is less affected by the outside temperature. The medium is preferably insulating and non-flammable.
[0235] By using the positive electrode active material described in the above embodiment for the positive electrode 604, it is possible to achieve high capacity and cycle. The cylindrical secondary battery 600 can be made to have excellent characteristics.
[0236] [Example of secondary battery structure] Another structural example of the secondary battery will be described with reference to FIGS.
[0237] 14(A) and 14(B) are diagrams showing the external appearance of a secondary battery. , and is connected to antenna 914 and antenna 915 via circuit board 900. In addition, a label 910 is attached to the secondary battery 913. As shown, the secondary battery 913 is connected to a terminal 951 and a terminal 952 .
[0238] The circuit board 900 includes a terminal 911 and a circuit 912. The terminal 911 is connected to a terminal 951. , a terminal 952, an antenna 914, an antenna 915, and a circuit 912. A plurality of terminals 911 are provided, and each of the plurality of terminals 911 is used as a control signal input terminal, a power supply terminal, etc. may also be used.
[0239] The circuit 912 may be provided on the back surface of the circuit board 900. The antenna 915 is not limited to a coil shape, but may be, for example, a wire shape or a plate shape. Planar antenna, aperture antenna, traveling wave antenna, EH antenna, magnetic field antenna, dielectric Alternatively, antenna 914 or antenna 915 may be used. The flat conductor may function as one of the conductors for electric field coupling. In other words, the annulus can be used as one of the two conductors of the capacitor. In this way, the electromagnetic field, the magnetic field, and the like can be detected by the antenna 914 or the antenna 915. Alternatively, power can be exchanged using an electric field.
[0240] The line width of antenna 914 is preferably larger than the line width of antenna 915. This allows the amount of power received by the antenna 914 to be increased.
[0241] The secondary battery has a layer 916 between the antenna 914 and the secondary battery 913, and between the antenna 915 and the secondary battery 913. The layer 916 has a function of shielding an electromagnetic field generated by the secondary battery 913, for example. The layer 916 may be made of, for example, a magnetic material.
[0242] The structure of the secondary battery is not limited to that shown in FIG.
[0243] For example, as shown in FIG. 15(A-1) and FIG. 15(A-2), In the secondary battery 913 shown in (B), an antenna may be provided on each of a pair of opposing surfaces. FIG. 15(A-1) is an external view showing one of the pair of surfaces, and FIG. 14(A) and 14(B) are external views showing the other of the pair of surfaces. The same parts as those of the secondary battery shown in FIG. 14(A) and FIG. 14(B) are the same as those of the secondary battery shown in FIG. The explanations can be used as appropriate.
[0244] As shown in FIG. 15(A-1), a layer 916 is sandwiched between one of a pair of surfaces of a secondary battery 913. As shown in FIG. 15(A-2), an antenna 914 is provided to connect a pair of surfaces of the secondary battery 913. An antenna 918 is provided on the other side of the layer 917. The layer 917 is, for example, a secondary battery 91 The layer 917 has a function of blocking the electromagnetic field generated by the magnetic material 3. can be used.
[0245] By adopting the above structure, the size of both the antenna 914 and the antenna 918 can be increased. The antenna 918 can perform data communication with an external device, for example. The antenna 918 has a shape that can be applied to the antenna 914, for example. A communication method between the secondary battery and other devices via an antenna 918. Examples of such communication methods include NFC (near field communication), which can be used between secondary batteries and other devices. It is possible to apply a response method that allows
[0246] Alternatively, as shown in FIG. 15(B-1), the secondary battery 9 shown in FIG. 14(A) and FIG. 14(B) may be used. A display device 920 may be provided in the display device 13. The display device 920 is electrically connected to the terminal 911. It is not necessary to provide the label 910 in the portion where the display device 920 is provided. 14(A) and 14(B), the same parts as those of the secondary battery shown in FIG. The description of the secondary battery shown in FIG. 14(B) can be used as appropriate.
[0247] The display device 920 displays, for example, an image indicating whether charging is in progress, an image indicating the amount of stored power, etc. The display device 920 may be, for example, an electronic paper, a liquid crystal display device, an electrophotographic display device, or the like. For example, an electroluminescence (EL) display device can be used. By using the par, the power consumption of the display device 920 can be reduced.
[0248] Alternatively, as shown in FIG. 15(B-2), the secondary battery 9 shown in FIG. 14(A) and FIG. 14(B) may be used. A sensor 921 may be provided on the sensor 13. The sensor 921 is connected to the terminal 911 via a terminal 922. The secondary battery shown in FIG. 14(A) and FIG. 14(B) is electrically connected to the same part. In this regard, the description of the secondary battery shown in FIG. 14(A) and FIG. 14(B) can be appropriately applied.
[0249] The sensor 921 may be, for example, a sensor for detecting displacement, position, speed, acceleration, angular velocity, number of rotations, distance, light, etc. , liquid, magnetic, temperature, chemical, sound, time, hardness, electric field, current, voltage, power, radiation, flow It is sufficient if the device has the function of measuring the amount, humidity, gradient, vibration, odor, or infrared rays. By providing the sensor 921, for example, data indicating the environment in which the secondary battery is placed can be obtained. It is also possible to detect a signal (such as temperature) and store it in memory within the circuit 912.
[0250] Further, a structural example of the secondary battery 913 will be described with reference to FIGS.
[0251] A secondary battery 913 shown in FIG. 16A has a terminal 951 and a terminal 952 provided inside a housing 930. The winding body 950 is impregnated with an electrolyte inside the housing 930. The terminal 952 is in contact with the housing 930, and the terminal 951 is in contact with the housing by using an insulating material or the like. In FIG. 16(A), for convenience, the housing 930 is not in contact with the 9, in reality, the winding body 950 is covered by the housing 930, and the terminals 951 and 95 2 extends outside the housing 930. The housing 930 is made of a metal material (e.g., aluminum). Materials such as rubber or resin materials can be used.
[0252] As shown in FIG. 16B, the housing 930 shown in FIG. 16A is made of a plurality of materials. For example, the secondary battery 913 shown in FIG. The wound body 930b is attached to the housing 930a. 50 are provided.
[0253] The housing 930a can be made of an insulating material such as an organic resin. By using a material such as organic resin on the surface on which the secondary battery 913 is formed, If the shielding of the electric field by the housing 930a is small, the shielding of the housing 930a can be suppressed. Antennas such as antenna 914 and antenna 915 may be provided inside the housing 930b. For example, a metal material can be used.
[0254] The structure of the wound body 950 is shown in FIG. The winding body 950 has a pole 932 and a separator 933. The negative electrode 931 and the positive electrode 932 are stacked on top of each other, and the laminated sheet is wound to form a wound body. The negative electrode 931, the positive electrode 932, and the separator 933 are laminated together. You can stack several of them.
[0255] The negative electrode 931 is connected to the terminal 911 shown in FIG. 14 via one of the terminals 951 and 952. The positive electrode 932 is connected to the terminal 91 shown in FIG. Connected to 1.
[0256] By using the positive electrode active material described in the above embodiment for the positive electrode 932, the battery can be cycled with a high capacity. The secondary battery 913 can have excellent characteristics.
[0257] [Laminated secondary battery] Next, an example of a laminated secondary battery will be described with reference to FIGS. If the laminated secondary battery is made flexible, the flexible portion is at least If the secondary battery is mounted on an electronic device that also has a battery, the secondary battery can be bent according to the deformation of the electronic device. can.
[0258] A laminated secondary battery 980 will be described with reference to FIG. The battery 980 has a wound body 993 shown in FIG. 17, a positive electrode 995, and a separator 996. Similar to the wound body 950, a negative electrode 994 and a positive electrode 995 are stacked with a separator 996 interposed therebetween. The laminated sheet is then wound.
[0259] The number of layers of the negative electrode 994, the positive electrode 995, and the separator 996 is determined as required. The negative electrode 994 is connected to the lead electrode 997 and the lead The positive electrode 995 is connected to a negative electrode collector (not shown) via one of the lead electrodes 998. The other of the electrode 997 and the lead electrode 998 is connected to a positive electrode current collector (not shown).
[0260] As shown in FIG. 18B, a film 981 that serves as an exterior body and a film 98 having a recess are 2 are bonded together by thermocompression or the like to form a space in which the above-mentioned wound body 993 is housed. In this way, a secondary battery 980 can be manufactured as shown in FIG. 3 has a lead electrode 997 and a lead electrode 998, a film 981, and a recess The inside of the film 982 is impregnated with an electrolyte.
[0261] The film 981 and the film 982 having the recesses are made of a metal material such as aluminum. The film 981 and the film 982 having the recesses can be made of a resin material. If a resin material is used as the material, when an external force is applied, the film 981 and the recessed portion The film 982 having the electrode can be deformed, and a flexible storage battery can be produced. can.
[0262] In addition, although Fig. 18(B) and Fig. 18(C) show an example in which two films are used, A space is formed by folding one sheet of film, and the above-mentioned wound body 99 is inserted into the space. It may also accommodate 3.
[0263] By using the positive electrode active material described in the previous embodiment for the positive electrode 995, it is possible to achieve high capacity cycling. The secondary battery 980 can have excellent characteristics.
[0264] In addition, in FIG. 18, a secondary battery 9 having a wound body in a space formed by a film serving as an exterior body is shown. We have explained the example of 80, but for example, as shown in Figure 19, The space defined by the positive electrode layer may be a space defined by a separator and a negative electrode. stomach.
[0265] The laminated secondary battery 500 shown in FIG. 19(A) includes a positive electrode current collector 501 and a positive electrode active material. A positive electrode 503 having a positive electrode active material layer 502, a negative electrode current collector 504 and a negative electrode active material layer 505. The battery includes a negative electrode 506, a separator 507, an electrolyte 508, and an exterior body 509. A separator 507 is provided between a positive electrode 503 and a negative electrode 506 provided in a body 509. The exterior body 509 is filled with an electrolyte 508. The electrolyte solution shown in the second embodiment can be used.
[0266] In the laminated secondary battery 500 shown in FIG. 19(A), a positive electrode current collector 501 and a negative electrode current collector The positive electrode current collector 504 also serves as a terminal for obtaining electrical contact with the outside. A part of the current collector 501 and the negative electrode current collector 504 is exposed to the outside from the exterior body 509. In addition, the positive electrode current collector 501 and the negative electrode current collector 504 may be arranged in a manner similar to that described above. Instead of exposing it to the outside, a lead electrode is used to connect the lead electrode to the positive electrode current collector 501 or the negative electrode The lead electrode may be exposed to the outside by ultrasonic bonding to the current collector 504 .
[0267] In the laminated secondary battery 500, the exterior body 509 is made of, for example, polyethylene, poly A film made of propylene, polycarbonate, ionomer, polyamide, etc. is coated with a A thin metal film with excellent flexibility, such as aluminum, stainless steel, copper, or nickel, is applied. On the metallic thin film, an insulating synthetic resin such as polyamide resin or polyester resin is applied as the outer surface of the exterior body. A laminate film having a three-layer structure with an oil film can be used.
[0268] An example of the cross-sectional structure of a laminated secondary battery 500 is shown in FIG. For simplicity, in A), an example consisting of two current collectors is shown, but in reality, As shown in FIG. 1, it is composed of multiple electrode layers.
[0269] In FIG. 19B, as an example, the number of electrode layers is 16. However, the secondary battery 500 has flexibility. In FIG. 19(B), the negative electrode current collector 504 has eight layers. The positive electrode current collector 501 has a structure of 8 layers, totaling 16 layers. The cross section of the extraction part is shown, and eight layers of negative electrode current collector 504 are ultrasonically bonded. The number of electrode layers is not limited to 16, and may be more or less. In addition, when the number of electrode layers is small, the secondary battery can have a larger capacity. In this case, a secondary battery can be made thin and has excellent flexibility.
[0270] An example of an external view of a laminated secondary battery 500 is shown in FIGS. 20 and 21. 21 shows a positive electrode 503, a negative electrode 506, a separator 507, an outer casing 509, a positive electrode lead The positive electrode 510 and the negative electrode 511 are connected to each other.
[0271] FIG. 22A shows an external view of a positive electrode 503 and a negative electrode 506. The positive electrode 503 is connected to a positive electrode current collector 50 1, and the positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. 503 has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab region). 506 has a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. In addition, the negative electrode 506 has a region where the negative electrode current collector 504 is partially exposed, that is, a tab region. The area and shape of the tab regions of the positive electrode and the negative electrode are not limited to the example shown in FIG. I can't.
[0272] [Method of manufacturing laminated secondary battery] Here, an example of a method for producing a laminated secondary battery shown in FIG. 20 will be described with reference to FIG. This will be explained using (B) and (C).
[0273] First, the negative electrode 506, the separator 507, and the positive electrode 503 are laminated. The negative electrode 506, the separator 507, and the positive electrode 503 are shown. Next, the bonding of the tab regions of the positive electrode 503 and the bonding of the tabs of the positive electrode on the outermost surface are shown. The positive electrode lead electrode 510 is bonded to the region. For example, ultrasonic welding or the like may be used for bonding. Similarly, the bonding between the tab regions of the negative electrodes 506 and the bonding of the negative electrode leads to the tab region of the outermost negative electrode are preferably performed. Then, the metal layer 511 is bonded.
[0274] Next, the negative electrode 506 , the separator 507 and the positive electrode 503 are placed on the exterior body 509 .
[0275] Next, as shown in FIG. 22(C), the exterior body 509 is folded at the portion indicated by the dashed line. After that, the outer periphery of the exterior body 509 is bonded. For example, thermocompression bonding may be used for bonding. 509, so that the electrolyte 508 can be poured in later. An area that is not joined (hereinafter referred to as an inlet) is provided.
[0276] Next, electrolyte 508 (not shown) is introduced into exterior body 509 through an inlet. The electrolyte 508 is introduced into the inside of the electrode 509 under a reduced pressure atmosphere or an inert atmosphere. Finally, the inlet is bonded. In this way, the laminated mold is The secondary battery 500 can be manufactured.
[0277] By using the positive electrode active material described in the above embodiment for the positive electrode 503, it is possible to achieve high capacity and cycle. The secondary battery 500 can have excellent characteristics.
[0278] [Bendable secondary battery] Next, an example of a bendable secondary battery will be described with reference to FIGS. 23 and 24. .
[0279] FIG. 23(A) shows a schematic top view of a bendable secondary battery 250. 23(A) and (B2) are cut along the lines C1-C2 and C3- 3C4 is a schematic cross-sectional view taken along the cutting line A1-A2. The battery has a positive electrode 211a and a negative electrode 211b housed inside an exterior body 251. A lead 212a electrically connected to the negative electrode 211a, and a lead 212b electrically connected to the negative electrode 211b. The wire 212b extends outside the exterior body 251. In addition to the positive electrode 211a and the negative electrode 211b, an electrolyte (not shown) is enclosed in the .
[0280] The positive electrode 211a and the negative electrode 211b of the secondary battery 250 will be described with reference to FIG. FIG. 24(A) shows the stacking order of the positive electrode 211a, the negative electrode 211b, and the separator 214. FIG. 24(B) shows a lead wire in addition to the positive electrode 211a and the negative electrode 211b. 2 is a perspective view showing the lead 212a and the lead 212b.
[0281] As shown in FIG. 24(A), the secondary battery 250 has a plurality of rectangular positive electrodes 211a, a plurality of short The battery has a strip-shaped negative electrode 211b and a plurality of separators 214. Each of the positive electrodes 211a and 211b has a protruding tab portion and a portion other than the tab. A positive electrode active material layer is formed on the portion of the surface other than the tab, and a negative electrode 211b is formed on the portion of the surface other than the tab. A negative electrode active material layer is formed thereon.
[0282] The surfaces of the positive electrode 211a on which the positive electrode active material layer is not formed and the surfaces of the negative electrode 211b on which the negative electrode active material layer is not formed are The positive electrode 211a and the negative electrode 211b are laminated so that the surfaces without the layer are in contact with each other. can be.
[0283] In addition, the surface of the positive electrode 211a on which the positive electrode active material is formed and the surface of the negative electrode 211b on which the negative electrode active material is formed are A separator 214 is provided between the two surfaces. 214 is shown by a dotted line.
[0284] As shown in FIG. 24B, the positive electrodes 211a and the leads 212a are connected to each other through a joint 215. The negative electrodes 211b and the leads 212b are electrically connected to each other at the joints 211a. Electrical connection is made at 15b.
[0285] Next, the exterior body 251 will be described with reference to FIGS. 23(B1), (B2), (C), and (D). do.
[0286] The exterior body 251 has a film-like shape and is arranged to sandwich the positive electrode 211a and the negative electrode 211b. The exterior body 251 is folded in two at the folded portion 261 and a pair of seal portions 2 The pair of sealing parts 262 are connected to the positive electrode 211a and the negative electrode 211b. The seal portion 26 is provided on either side of the electrode 211b and can also be called a side seal. 3 has a portion overlapping with the lead 212a and the lead 212b, and is also called a top seal. This can be done.
[0287] The exterior body 251 has a ridge line 271 and a valley line 272 at the portion overlapping the positive electrode 211a and the negative electrode 211b. It is preferable that the sealing portion 26 of the exterior body 251 has a corrugated shape in which the grooves 72 are arranged alternately. 2 and the seal portion 263 are preferably flat.
[0288] FIG. 23(B1) is a cross section cut at the portion overlapping with the ridge line 271, and FIG. 23(B2) is a cross section cut at the portion overlapping with the ridge line 271. The cross section is taken at the part overlapping with the valley line 272. It corresponds to a cross section in the width direction of the battery 250, the positive electrode 211a, and the negative electrode 211b.
[0289] Here, the ends in the width direction of the positive electrode 211a and the negative electrode 211b, i.e., the positive electrode 211a and The distance between the end of the negative electrode 211b and the seal portion 262 is defined as La. When the electrode 211 is bent or otherwise deformed, the positive electrode 211a and the negative electrode 211b are elongated as described below. In this case, if the distance La is too short, the exterior body 251 and the The positive electrode 211a and the negative electrode 211b may rub against each other strongly, and the exterior body 251 may be damaged. In particular, if the metal film of the exterior body 251 is exposed, the metal film may be corroded by the electrolyte. Therefore, it is preferable to set the distance La as long as possible. On the other hand, if the distance La is made too large, the volume of the secondary battery 250 increases.
[0290] In addition, the greater the total thickness of the laminated positive electrodes 211a and negative electrodes 211b, the greater the It is preferable to increase the distance La between the negative electrode 211a and the seal portion 262. .
[0291] More specifically, the laminated positive electrode 211a and negative electrode 211b and a separator (not shown) are When the total thickness of the data 214 is t, the distance La is 0.8 to 3.0 times the thickness t. Preferably, the ratio is 0.9 to 2.5 times, more preferably 1.0 to 2.0 times. By setting the distance La in this range, the device is compact and has good resistance to bending. This makes it possible to realize a highly reliable battery.
[0292] In addition, when the distance between the pair of seal portions 262 is a distance Lb, the distance Lb is and is sufficiently larger than the width of the negative electrode 211b (here, the width Wb of the negative electrode 211b). This is preferable. When the secondary battery 250 is repeatedly bent or deformed, Even if the positive electrode 211a and the negative electrode 211b come into contact with the exterior body 251, the positive electrode 211a and the negative electrode Since a part of the electrode 211b can be shifted in the width direction, the positive electrode 211a and the negative electrode 211b This effectively prevents the exterior body 251 from rubbing against each other.
[0293] For example, the difference between the distance Lb between the pair of seal portions 262 and the width Wb of the negative electrode 211b is 1.6 times or more and 6.0 times or less, preferably 1.8 times, the thickness t of the negative electrode 211a and the negative electrode 211b It is preferable that the ratio is 2.0 to 4.0 times. .
[0294] In other words, it is preferable that the distance Lb, the width Wb, and the thickness t satisfy the relationship of the following formula 1. It is nice.
[0295]
number
[0296] Here, a is 0.8 or more and 3.0 or less, preferably 0.9 or more and 2.5 or less, and more preferably is greater than or equal to 1.0 and less than or equal to 2.0.
[0297] FIG. 23C is a cross section including the lead 212a, and shows the secondary battery 250, the positive electrode 211a, 23(C), the bending portion 211a corresponds to a cross section of the negative electrode 211b in the longitudinal direction. In the portion 261, the ends of the positive electrode 211a and the negative electrode 211b in the length direction and the exterior body 251 It is preferable to have a space 273 therebetween.
[0298] FIG. 23(D) shows a schematic cross-sectional view of the secondary battery 250 when bent. corresponds to the cross section taken along line B1-B2 in FIG. 23(A).
[0299] When the secondary battery 250 is bent, a part of the exterior body 251 located on the outside of the bend stretches, and a part located on the inside More specifically, the other part located on the outside of the exterior body 251 is deformed so as to shrink. The portion deforms so that the amplitude of the wave becomes smaller and the period of the wave becomes larger. The part located inside 51 is deformed so that the wave amplitude is large and the wave period is small. In this way, the exterior body 251 is deformed, and the exterior body 251 is bent. Since the stress is relieved, the material that constitutes the exterior body 251 does not need to expand or contract. As a result, the exterior body 251 is not damaged, and the secondary battery 250 can be bent with a small force. Cut.
[0300] Furthermore, as shown in FIG. 23(D), when the secondary battery 250 is bent, the positive electrode 211a and the negative electrode At this time, the multiple stacked positive electrodes 211a and 211b are shifted relative to each other. The negative electrode 211b is fixed at one end on the seal portion 263 side by the fixing member 217. The amount of deviation increases toward the bent portion 261. The stress applied to the positive electrode 211a and the negative electrode 211b is relieved, and the positive electrode 211a and the negative electrode 211b As a result, the positive electrode 211a and the negative electrode 211b do not need to be damaged. Therefore, the secondary battery 250 can be bent without any bending.
[0301] In addition, a space 273 is provided between the positive electrode 211a and the negative electrode 211b and the exterior body 251. As a result, the positive electrode 211a and the negative electrode 211b located on the inner side when bent are attached to the exterior body 251. can be displaced relative to one another without contacting each other.
[0302] The secondary battery 250 illustrated in FIG. 23 and FIG. 24 has a casing that can withstand repeated bending and straightening. The body, the positive electrode 211a and the negative electrode 211b, etc. are unlikely to be damaged, and the battery characteristics are also unlikely to deteriorate. The secondary battery 250 has a positive electrode 211a having the same structure as described in the previous embodiment. By using a positive electrode active material, a battery having even better cycle characteristics can be obtained.
[0303] (Embodiment 4) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on an electronic device will be described. do.
[0304] First, as described in part of the third embodiment, a bendable secondary battery is mounted on an electronic device. Examples are shown in Figures 25(A) to 25(G). Examples of devices include television sets (also called televisions or television receivers); Computer monitors, digital cameras, digital video cameras, digital photos Frame, mobile phone (also called mobile phone or mobile phone device), portable game machine, portable information Examples include terminals, audio playback devices, and large game machines such as pachinko machines.
[0305] In addition, the flexible secondary battery can be mounted on the inner or outer walls of houses or buildings, or on the inside or outside of automobiles. It is also possible to incorporate it along the curved surfaces of the interior or exterior of the vehicle.
[0306] FIG. 25A shows an example of a mobile phone. A mobile phone 7400 includes a housing 7401. In addition to the display unit 7402, operation buttons 7403, an external connection port 7404, The mobile phone 7400 is equipped with a speaker 7405, a microphone 7406, etc. The secondary battery 7407 is a secondary battery of one embodiment of the present invention. This makes it possible to provide a lightweight mobile phone with a long life.
[0307] FIG. 25B shows the mobile phone 7400 in a curved state. When the battery is deformed by applying an external force to the battery, the secondary battery installed inside the battery is released. The secondary battery 7407 is also bent. At this time, the state of the bent secondary battery 7407 is shown in FIG. The secondary battery 7407 is a thin storage battery. The secondary battery 7407 is in a bent state. The secondary battery 7407 is fixed in place by a lead electrode electrically connected to the current collector. For example, the current collector is made of copper foil, and some of it is alloyed with gallium to form a layer in contact with the current collector. The adhesiveness between the active material layer and the secondary battery 7407 is improved, and the secondary battery 7407 has a highly reliable structure when bent. It has become a success.
[0308] FIG. 25D shows an example of a bangle-type display device. The portable display device 7100 is The device includes a housing 7101 , a display unit 7102 , operation buttons 7103 , and a secondary battery 7104 . FIG. 25(E) shows the bent state of the secondary battery 7104. When the device is attached to the user's arm, the housing may deform and cause damage to part of the secondary battery 7104 or The total curvature changes. Note that the degree of curvature at any point on the curve is expressed as the radius of the corresponding circle. The value expressed is called the radius of curvature, and the inverse of the radius of curvature is called the curvature. Within the range of 40 mm to 150 mm, a part of the main surface of the case or the secondary battery 7104 The radius of curvature of the main surface of the secondary battery 7104 is 40 mm or more and 150 mm or less. If the thickness is within the range of 1 mm or less, high reliability can be maintained. By using the secondary battery of one embodiment, a lightweight, long-life portable display device can be provided.
[0309] FIG. 25(F) shows an example of a wristwatch-type portable information terminal. The portable information terminal 7200 is , a housing 7201, a display unit 7202, a band 7203, a buckle 7204, and an operation button 72 05, input / output terminal 7206, etc.
[0310] The portable information terminal 7200 is capable of carrying out mobile telephone calls, e-mails, viewing and creating documents, playing music, and using the Internet. - It can run various applications such as internet communication and computer games. do.
[0311] The display unit 7202 has a curved display surface, and displays images along the curved display surface. The display portion 7202 is provided with a touch sensor, and can be used to input a touch signal to the screen using a finger or a stylus. For example, the icon 72 displayed on the display unit 7202 can be operated by touching it. You can launch the application by touching 07.
[0312] The operation button 7205 is used to set the time, turn the power on and off, and turn wireless communication on and off. It has various functions such as operation, silent mode activation and deactivation, power saving mode activation and deactivation, etc. For example, an operating system installed in the portable information terminal 7200 can The function of the operation button 7205 can also be freely set using the stem.
[0313] In addition, the mobile information terminal 7200 is capable of performing short-distance wireless communication according to a communication standard. For example, by communicating with a wireless headset, a hands-free You can also make calls.
[0314] The portable information terminal 7200 also includes an input / output terminal 7206, and a connector for connecting to other information terminals. Data can be exchanged directly through the input / output terminal 7206. The charging operation can be performed by wireless power supply without going through the input / output terminal 7206. It is also possible.
[0315] A display portion 7202 of a portable information terminal 7200 includes a secondary battery of one embodiment of the present invention. By using the secondary battery of one embodiment of the present invention, a lightweight portable information terminal with a long life can be provided. For example, the secondary battery 7104 shown in FIG. 25E is curved inside the housing 7201. or may be incorporated in a bendable state inside the band 7203.
[0316] The portable information terminal 7200 preferably has a sensor. For example, a fingerprint sensor may be used as the sensor. Sensors for human body such as pulse sensors, body temperature sensors, touch sensors, pressure sensors, acceleration sensors It is preferable that the above-mentioned components are mounted on the vehicle.
[0317] FIG. 25G shows an example of a wristband-type display device. The display device 7300 includes a display unit 7 The display device 7300 includes a display 304 and a secondary battery of one embodiment of the present invention. The display unit 7304 may be equipped with a touch sensor, and may function as a portable information terminal. It is also possible.
[0318] The display surface of the display unit 7304 is curved, and the display can be performed along the curved display surface. In addition, the display device 7300 can display a display state by short-distance wireless communication according to a communication standard. The situation can be changed.
[0319] The display device 7300 also has an input / output terminal, and can directly connect to other information terminals via a connector. It is also possible to charge the device via the input / output terminals. The charging operation may be performed by wireless power supply without going through the input / output terminals.
[0320] By using the secondary battery of one embodiment of the present invention as the secondary battery included in the display device 7300, It is possible to provide a display device with a long life and low cost.
[0321] FIG. 1 shows an example in which the secondary battery having excellent cycle characteristics shown in the above embodiment is mounted on an electronic device. 25(H), and Figs. 26 and 27.
[0322] By using the secondary battery of one embodiment of the present invention as a secondary battery in everyday electronic devices, the device can be lightweight and have a long life. For example, we can provide a wide range of products for daily electronic devices, such as electric toothbrushes, electric shavers, These include mobile beauty devices, and the secondary batteries for these products are designed to be easy for users to carry. Therefore, there is a demand for a stick-shaped secondary battery that is small, lightweight, and has a large capacity.
[0323] FIG. 25(H) is a perspective view of a device also called a tobacco-containing smoking device (electronic cigarette). In 25(H), the electronic cigarette 7500 is an atomizer 7501 that includes a heating element and an atomizer A secondary battery 7504 that supplies power to the myza, and a cart including a liquid supply bottle and sensors, etc. The secondary battery 7504 is composed of a ridge 7502. To enhance safety, the secondary battery 7504 is protected from overcharging and overcharging. A protection circuit for preventing discharge may be electrically connected to the secondary battery 7504. The secondary battery 7504 has an external terminal so that it can be connected to a charging device. The 504 is the tip when held, so the total length is short and the weight is light. Since the secondary battery of one embodiment of the present invention has a high capacity and good cycle characteristics, We offer the 7500 electronic cigarette, which is small and lightweight and can be used for long periods of time. Can be provided.
[0324] Next, FIG. 26(A) and FIG. 26(B) show an example of a foldable tablet terminal. The tablet terminal 9600 shown in FIG. 26(A) and FIG. 26(B) includes a housing 9630. a, housing 9630b, a movable part 9640 connecting the housing 9630a and the housing 9630b, A display unit 9631 having a display unit 9631a and a display unit 9631b, a switch 9625 to a switch The display unit 9631 has a switch 9627, a fastener 9629, and an operation switch 9628. By using a flexible panel, it is possible to create a tablet terminal with a larger display area. FIG. 26(A) shows a tablet terminal 9600 in an open state, and FIG. 9B) shows the tablet terminal 9600 in a closed state.
[0325] The tablet terminal 9600 also includes a battery storage device inside the housing 9630a and the housing 9630b. The power storage unit 9635 is connected to the housing 9630a through the movable portion 9640. It is located across 9630b.
[0326] The display unit 9631 can be entirely or partially used as a touch panel. By touching images, text, input forms, etc., including icons displayed in the area, data For example, a keyboard is provided on the entire surface of the display portion 9631a on the housing 9630a side. The button is displayed to display information such as text and images on the display unit 9631b on the housing 9630b. may be displayed and used.
[0327] In addition, a keyboard is displayed on the display unit 9631b on the housing 9630b side. The display unit 9631a on the side of the camera may be used to display information such as text and images. The 9631 is equipped with a touch panel keyboard display switch button. By touching the button with your finger or a stylus, the keyboard will be displayed on the display 9631. You may do so.
[0328] In addition, the touch panel area of the display unit 9631a on the housing 9630a side and the touch panel area of the display unit 9631b on the housing 9630b side Simultaneous touch input can also be made to the touch panel area of the display portion 9631b.
[0329] In addition, the switches 9625 to 9627 are used to operate the tablet terminal 9600. It is not only an interface for using the For example, at least one of the switches 9625 to 9627 may be One acts as a switch to turn the power of the Tablet 9600 on and off. Also, for example, at least one of the switches 9625 to 9627 may be The ability to switch between horizontal and vertical display orientation, or between black and white and color display In addition, for example, at least one of the switches 9625 to 9627 may have a function of At least one of the display units 9631 may have a function of adjusting the luminance of the display unit 9631. The brightness of 1 is the external brightness during use detected by a light sensor built into the tablet terminal 9600. It can be optimized according to the amount of light. Note that the tablet device is a light sensor. In addition, it also has other detection devices such as gyro, acceleration sensor, etc. that detect tilt. It may be allowed.
[0330] In FIG. 26A, a display portion 9631a on the housing 9630a side and a display portion 9631b on the housing 9630b side are 9 shows an example in which the display area of the display unit 9631a and the display unit 9631b are substantially the same. The display area of each of 631b is not particularly limited, and one size may be different from the other. The display quality may be different, e.g. one with higher resolution than the other. The display panel may also be capable of displaying images.
[0331] FIG. 26B shows a tablet terminal 9600 folded in half. The terminal 9600 includes a housing 9630, a solar cell 9633, and a DC-DC converter 9636. A charge and discharge control circuit 9634 including a power storage unit 9635 is also provided. A storage battery is used.
[0332] As mentioned above, the tablet terminal 9600 can be folded in half, so when not in use, The housing 9630a and the housing 9630b can be folded so as to overlap each other. By folding the tablet terminal 9600, the display portion 9631 can be protected, and therefore the durability of the tablet terminal 9600 can be improved. In addition, the power storage unit 9635 using the secondary battery of one embodiment of the present invention can have high The tablet has a large capacity and good cycle characteristics, allowing it to be used for a long period of time. A portable terminal 9600 can be provided.
[0333] In addition, the tablet terminal 9600 shown in FIG. 26(A) and FIG. 26(B) , the ability to display various information (still images, videos, text images, etc.), calendars, dates, or The function to display the time, etc. on the display, and to operate or edit the information displayed on the display by touch input touch input function, function to control processing by various software (programs), etc. may have the following structure:
[0334] The tablet terminal 9600 is equipped with a solar cell 9633 on its surface, which provides power to the touch screen. The solar cell 963 can supply the solar cell 963 with the panel, the display unit, or the image signal processing unit. 3 can be provided on one or both sides of the housing 9630, and can efficiently charge the power storage unit 9635. The power storage unit 9635 can be a lithium ion battery. The use of such a structure has the advantage of enabling miniaturization.
[0335] The configuration and operation of the charge / discharge control circuit 9634 shown in FIG. A block diagram is shown in FIG. 26C. 5, DC-DC converter 9636, converter 9637, switches SW1 to SW3, table The display unit 9631 is shown, which includes a storage battery 9635, a DC-DC converter 9636, and a The inverter 9637 and the switches SW1 to SW3 are connected to the charge / discharge control circuit 96 shown in FIG. This corresponds to 34.
[0336] First, an example of operation in which power is generated by the solar cell 9633 using external light will be described. The power generated by the solar cell is converted to a voltage for charging the storage battery 9635 by the DCDC controller. The voltage is increased or decreased by a inverter 9636. When power from the 9633 is used, switch SW1 is turned on and the converter 9637 The voltage is increased or decreased to a voltage required for the display unit 9631. When not displaying the battery status, turn SW1 off and SW2 on to charge the battery 9635. The configuration may be such that the power supply is electrically connected to the power source.
[0337] The solar cell 9633 is shown as an example of a power generating means, but is not limited thereto. Storage of electricity by other power generation means such as piezoelectric elements and thermoelectric conversion elements For example, the device may be configured to transmit and receive power wirelessly (contactlessly). It is also possible to combine it with a non-contact power transmission module that charges the battery by using other charging methods. This is also fine.
[0338] FIG. 27 shows another example of electronic equipment. In FIG. 27, a display device 8000 according to one embodiment of the present invention is 8 is an example of an electronic device using a secondary battery 8004 according to an embodiment. 8000 corresponds to a display device for receiving TV broadcasts, and includes a housing 8001, a display unit 8002, and a speaker unit. The secondary battery 8004 according to one embodiment of the present invention includes a housing. The display device 8000 is provided inside a body 8001. The display device 8000 receives power from a commercial power source. Alternatively, the power stored in the secondary battery 8004 can be used. Even when power cannot be supplied from a commercial power source due to a power outage or the like, the present invention according to one embodiment of the present invention can be used. By using the secondary battery 8004 as an uninterruptible power supply, the display device 8000 can be used. do.
[0339] The display unit 8002 may be a liquid crystal display device, an emitting device having light emitting elements such as organic EL elements in each pixel, or the like. Device, electrophoretic display device, DMD (Digital Micromirror Devi ce), PDP (Plasma Display Panel), FED (Field A semiconductor display device such as a 3D Emission Display can be used.
[0340] In addition, display devices are used for TV broadcast reception, personal computers, advertising displays, etc. , all display devices for displaying information are included.
[0341] In FIG. 27, a stationary lighting device 8100 includes a secondary battery 81 according to one embodiment of the present invention. 8101, a light source 8102, and a light source 8103 are used. 27, the secondary battery 8103 is disposed in the housing 81. 8102 is installed inside a ceiling 8104. However, the secondary battery 8103 may be provided inside the housing 8101. The device 8100 can receive power from a commercial power source, or store power in a secondary battery 8103. Therefore, when the power supply from the commercial power source is cut off due to a power outage, Even when the electricity cannot be received, the secondary battery 8103 according to one embodiment of the present invention is used as an uninterruptible power source. This enables the lighting device 8100 to be used.
[0342] In addition, FIG. 27 illustrates a lighting device 8100 that is installed on a ceiling 8104. However, in the secondary battery according to one embodiment of the present invention, other than the ceiling 8104, for example, the side wall 8105, the floor 8106, 106, the window 8107, etc., can be used as a fixed lighting device, or a tabletop lighting device. The present invention can also be used in lighting devices of this type.
[0343] In addition, the light source 8102 may be an artificial light source that artificially obtains light using electricity. Specifically, incandescent lamps, fluorescent lamps and other discharge lamps, light emitting diodes (LEDs) and organic electroluminescence (EL) elements The element is an example of the artificial light source.
[0344] In FIG. 27, an air conditioner having an indoor unit 8200 and an outdoor unit 8204 is as follows: 8 is an example of an electronic device using a secondary battery 8203 according to one embodiment of the present invention. The device 8200 includes a housing 8201, an air outlet 8202, a secondary battery 8203, and the like. 8 illustrates an example in which the secondary battery 8203 is provided in the indoor unit 8200. The battery 8203 may be provided in the outdoor unit 8204. A secondary battery 8203 may be provided in both the power source 8202 and the power source 8204. The power supply can be provided from a commercial power source, or the power stored in the secondary battery 8203 can be used. In particular, a secondary battery 82 is provided in both the indoor unit 8200 and the outdoor unit 8204. If 03 is installed, when power cannot be supplied from the commercial power source due to a power outage, etc. In addition, by using the secondary battery 8203 according to one embodiment of the present invention as an uninterruptible power supply, The conditioner can be used.
[0345] In Figure 27, a separate type air conditioner consisting of an indoor unit and an outdoor unit is shown. As an example, an all-in-one air conditioner that has both indoor and outdoor unit functions in a single housing. The secondary battery according to one embodiment of the present invention can also be used for the conditioner.
[0346] In FIG. 27, an electric refrigerator-freezer 8300 includes a secondary battery 8304 according to one embodiment of the present invention. Specifically, an electric refrigerator-freezer 8300 includes a housing 8301, a refrigerator It has a storage compartment door 8302, a freezer compartment door 8303, a secondary battery 8304, etc. A secondary battery 8304 is provided inside the housing 8301. The electric refrigerator-freezer 8300 is It can receive power from a commercial power source, or use the power stored in the secondary battery 8304. Therefore, when power cannot be supplied from commercial power sources due to a power outage, etc. However, by using the secondary battery 8304 according to one embodiment of the present invention as an uninterruptible power supply, It will be possible to use the 8300 freezer refrigerator.
[0347] Among the above-mentioned electronic devices, high-frequency heating devices such as microwave ovens, electric rice cookers, etc. The equipment requires high power for a short period of time. Therefore, the equipment supplements the power that cannot be supplied by commercial power sources. By using a secondary battery according to one embodiment of the present invention as an auxiliary power source for It can prevent the commercial power breaker from tripping during use.
[0348] In addition, during periods when electronic devices are not in use, especially during periods when the total amount of power that can be supplied by commercial power suppliers is low, During times when the ratio of electricity actually used (called the electricity usage rate) is low, By storing power in the battery, it is possible to prevent high power usage outside of the above time periods. For example, in the case of the electric refrigerator-freezer 8300, when the temperature is low, the refrigerator compartment door 830 2. During the night when the freezer door 8303 is not opened or closed, the secondary battery 8304 stores electricity. Then, as the temperature rises, the refrigerator door 8302 and the freezer door 8303 are opened and closed. During the daytime, when the vehicle is turned on, the secondary battery 8304 is used as an auxiliary power source, and the daytime power usage rate is can be kept low.
[0349] According to one embodiment of the present invention, the cycle characteristics of a secondary battery are improved, and the reliability is improved. Moreover, according to one aspect of the present invention, a high-capacity secondary battery can be obtained, and therefore This improves the characteristics of the secondary battery, thereby making it possible to reduce the size and weight of the secondary battery itself. Therefore, the secondary battery according to one embodiment of the present invention can be used in the electronic devices described in this embodiment. By incorporating the above, it is possible to provide an electronic device with a longer life and a lighter weight. The embodiment can be implemented in appropriate combination with other embodiments.
[0350] (Embodiment 5) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on a vehicle will be described.
[0351] When a secondary battery is installed in a vehicle, it becomes a hybrid vehicle (HEV), electric vehicle (EV), or powertrain. This will make it possible to realize next-generation clean energy vehicles such as plug-in hybrid vehicles (PHEVs). .
[0352] FIG. 28 illustrates an example of a vehicle using a secondary battery according to one embodiment of the present invention. The automobile 8400 shown in FIG. 1 is an electric automobile that uses an electric motor as a power source for driving. Alternatively, an electric motor and an engine can be selected as the power source for driving. By using one embodiment of the present invention, the cruising distance can be extended. In addition, the automobile 8400 has a secondary battery. 13(C) and 13(D) are mounted on the floor of the vehicle. In addition, a battery pack using multiple secondary batteries as shown in FIG. The secondary battery may be installed on the floor of the vehicle. In addition, it supplies power to light-emitting devices such as headlights 8401 and room lights (not shown). It can be provided.
[0353] In addition, the secondary battery is used for the display of the speedometer, tachometer, etc. of the automobile 8400. The secondary battery can supply power to the navigation device of the automobile 8400. The present invention can provide power to semiconductor devices such as power distribution systems.
[0354] The automobile 8500 shown in FIG. 28(B) is a secondary battery that is plugged in. The device can be charged by receiving power from an external charging facility using a contactless charging method or other methods. FIG. 28(B) shows a diagram of a charging device 8021 installed on the ground and a charging station 8022 installed on a vehicle 8500. The secondary battery 8024 is shown being charged via a cable 8022. For charging methods and connector specifications, please refer to the designated specifications of CHAdeMO (registered trademark) or Combo. The charging device 8021 is a charging station installed in a commercial facility. For example, plug-in technology can be used to The secondary battery 8024 installed in the automobile 8500 can be charged by the power supply. Charging is performed by converting AC power to DC power via a conversion device such as an ACDC converter. It is possible.
[0355] Although not shown, a power receiving device is mounted on the vehicle and receives power from a ground power transmitting device in a non-contact manner. In this non-contact power supply method, a power transmission device is installed on the road or exterior wall. By incorporating this technology, charging can be done not only when the vehicle is stopped but also while it is moving. Using this method, electric power may be transmitted between vehicles. A solar battery may be installed to charge the secondary battery when the vehicle is stopped or running. The power can be supplied using an electromagnetic induction method or a magnetic resonance method.
[0356] FIG 28C shows an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. The scooter 8600 shown in (C) has a secondary battery 8602, side mirrors 8601, and a turn signal. The secondary battery 8602 can supply electricity to the direction indicator light 8603. can.
[0357] In addition, the scooter 8600 shown in FIG. 28(C) has a secondary battery 860 in the storage space under the seat 8604. 2 can be stored. The secondary battery 8602 can be stored in the under-seat storage 8604 even if it is small. The secondary battery 8602 can be removed and stored in the under-seat storage 8604. When charging, the secondary battery 8602 is brought indoors, charged, and stored before driving. Just do that.
[0358] According to one aspect of the present invention, the cycle characteristics of the secondary battery are improved, and the capacity of the secondary battery is increased. Therefore, the secondary battery itself can be made smaller and lighter. If the body can be made smaller and lighter, it will contribute to reducing the weight of the vehicle, which will improve the driving range. In addition, the secondary battery installed in the vehicle can be used as a power supply source for other purposes besides the vehicle. In this case, for example, it is possible to avoid using commercial power sources during peak power demand periods. If we can avoid using commercial power sources during peak power demand periods, we can save energy and reduce secondary This can contribute to reducing carbon dioxide emissions. In addition, if the cycle characteristics are good, Since the batteries can be used for a long period of time, the amount of rare metals used, including cobalt, can be reduced. It is possible.
[0359] This embodiment mode can be implemented in appropriate combination with other embodiment modes. EXAMPLES
[0360] In this example, a positive electrode active material according to one embodiment of the present invention and a positive electrode active material according to a comparative example were prepared, and the XP The characteristics were analyzed using S, SEM and XRD. The sex was evaluated.
[0361] [Preparation of positive electrode active material] <Sample 1> In Sample 1, a semiconductor having cobalt as a transition metal was prepared by the method shown in FIG. 2 of the first embodiment. First, the molar ratio of LiF and MgF2 was LiF:MgF2=1: The mixture was weighed out so that the total weight was 3, and acetone was added as a solvent, followed by wet mixing and grinding. The powder was crushed in a ball mill using zirconia balls at 150 rpm for 1 hour. The treated material was collected and used as the first mixture (steps S11 to S14 in FIG. 2). ).
[0362] The particle size distribution of LiF and MgF2 before mixing and the first mixture after mixing are shown in FIG. The particle size distribution was measured using a laser diffraction particle size distribution analyzer, SALD-2200 (Shimadzu Corporation). The first mixture had a D50 of 3.561 μm and a mode diameter of 4.008 μm. From FIG. 29 and these results, it can be seen that the first mixture was sufficiently micronized. It was done.
[0363] In sample 1, lithium cobalt oxide was synthesized in advance and was obtained from Japan Chemical Industry Co., Ltd. CellSeed C-10N manufactured by CellSeed Co., Ltd. was used (step S25 in FIG. 2). As described in the first embodiment, the cobalt oxide has a D50 of about 12 μm and is low in impurities. It is lithium.
[0364] Next, the ratio of magnesium atoms contained in the first mixture to the molecular weight of lithium cobalt oxide is calculated. The mixture was weighed out so that the amount was 0.5 atomic % and mixed in a dry state. Zirconia balls were used for mixing. The mixture was ball milled at 150 rpm for 1 hour. The treated material was collected and used as a second mixture. (Steps S31 to S33 in FIG. 2).
[0365] Next, the second mixture was placed in an alumina crucible and heated at 850° C. and 60° C. in a muffle furnace in an oxygen atmosphere. The alumina crucible was covered during annealing. The oxygen flow rate was 10 L. The temperature was increased at 200°C / hr and decreased over 10 hours. The treated material was used as the positive electrode active material of Sample 1 (steps S34 and S35 in FIG. 2). ).
[0366] <Sample 2> The sample was prepared in the same manner as Sample 1, except that the annealing time in step S34 of FIG. 2 was set to 2 hours. The product thus produced was designated as Sample 2 (Comparative Example).
[0367] <<Sample 3>> The sample was fabricated in the same manner as Sample 1, except that annealing was not performed in step S34 of FIG. The result was designated as Sample 3 (Comparative Example).
[0368] <Sample 4> Cobalt oxide not subjected to any particular treatment (steps S31 to S35 in FIG. 2 are not performed) Lithium (CellSeed C-10N) was used as sample 4 (comparative example).
[0369] <Sample 5> In sample 5, lithium cobalt oxide was synthesized in advance and was obtained from the Japan Chemical Industry Co., Ltd. CellSeed C-5H manufactured by CellSeed Corporation was used (step S25 in FIG. 2). The other conditions were the same as for sample 1. Made.
[0370] <Sample 6> Lithium cobalt oxide without any special treatment (without steps S31 to S35) The cell seed C-5H was used as sample 6 (comparative example).
[0371] <Sample 7> In sample 7, a magnesium source and a fluorine source were added to the lithium cobalt oxide starting material. The lithium cobalt oxide containing magnesium and fluorine was synthesized by baking. The survey was conducted.
[0372] Specifically, lithium carbonate is used as the lithium source, cobalt oxide is used as the cobalt source, and magnesium is used as the Magnesium oxide is used as the ammonium source, lithium fluoride is used as the fluorine source, and the atomic ratio is Li Co 0.99 Mg 0.01 O 1.98 F 0.02 and mixed in a ball mill. did.
[0373] The mixture was then placed in an alumina crucible, covered, and heated in a muffle furnace in a dry air atmosphere for 95 The sample was baked at 0°C for 10 hours. The flow rate of dry air was 10 L / min. The temperature was increased at 200°C / h. The temperature was lowered for more than 10 hours. After the heat treatment, the material was mixed with magnesium and fluorine. The lithium cobalt oxide was
[0374] Next, lithium cobalt oxide containing magnesium and fluorine was placed in an alumina crucible and the lid was placed on it. The specimen was then annealed in an oxygen atmosphere at 800°C for 2 hours in a muffle furnace. The oxygen flow rate was 10 L. The temperature was increased at 200°C / hr and decreased over 10 hours. The treated material was designated as Sample 7.
[0375] <Sample 8> The lithium cobalt oxide (commercially available) containing magnesium and fluorine (Nippon Chemical Industry Co., Ltd.) was The aluminum crucible was then covered with a lid and placed in a muffler in an oxygen atmosphere. The sample was annealed in a furnace at 800°C for 2 hours. The oxygen flow rate was 10 L / min. The temperature was increased by 2 The temperature was lowered at 00°C / hr over 10 hours. It was decided.
[0376] <Sample 9> No particular processing is performed (steps S31 to S35 are not performed), magnesium and Lithium cobalt oxide containing fluorine (Cellseed C-20F, manufactured by Nippon Chemical Industry Co., Ltd.) was used as a sample. The result was named Pull 9 (comparative example).
[0377] <Sample 10> In sample 10, the lithium cobalt oxide was synthesized using Aldrich Co. Lithium barium oxide (catalog No. 442704, D50 is about 11 μm) was used (Figure 2, step S25). Also, in step S34 of FIG. 2, annealing is performed at 850° C. for 20 The other conditions were the same as for Sample 1.
[0378] <<Sample 11>> Lithium cobalt oxide without any special treatment (without steps S31 to S35) The resulting mixture was used as Sample 11 (Comparative Example) (Aldrich Co., No. 442704).
[0379] <Sample 12> Sample 12 (comparison example) is a pre-synthesized lithium cobalt oxide (LiCO3) manufactured by Nippon Kayaku Co., Ltd. CellSeed C-5hV (D50 is about 6 μm) manufactured by Gakushu Kogyo Co., Ltd. was used (step S2 in FIG. 2). 5) This is lithium cobalt oxide containing about 5100 ppm wt of titanium as an impurity. In step S34 of FIG. 2, annealing was performed at 800° C. for 2 hours. The preparation conditions were the same as for Sample 1.
[0380] <<Sample 13>> Sample 13 (comparative example) was annealed at 850° C. and 6 The sample was prepared in the same manner as Sample 12, except that the time was 0 hours.
[0381] <<Sample 14>> Lithium cobalt oxide without any special treatment (without steps S31 to S35) The sintered body (Cellseed C-5hV manufactured by Nippon Chemical Industry Co., Ltd.) was used as Sample 14 (Comparative Example).
[0382] <<Sample 15>> In sample 15 (comparison example), lithium cobalt oxide (Nihon Kagaku Kogyo Co., Ltd.) was used. A layer containing aluminum was applied to the surface of the cell (CellSeed C-5H manufactured by CellSeed Co., Ltd.) by the sol-gel method. After formation, it was annealed at 500° C. for 2 hours.
[0383] Specifically, aluminum isopropoxide and 2-propanol were mixed and cobalt was added to the mixture. Lithium tritate (C-5H) was added. At this time, the ratio of aluminum to lithium cobalt oxide was The weight of the mixture was adjusted to 0.0092 times that of the isopropoxide. The mixture was stirred in a thermostatic chamber with a humidity of 90%, and the mixture was dissolved in H2O and aluminum isopropoxide. The lithium cobalt oxide was reacted with the aluminum oxide to form an aluminum-containing layer on the surface of the lithium cobalt oxide. The precipitate was collected by filtration and dried under reduced pressure at 70° C. for 1 hour.
[0384] The lithium cobalt oxide having the aluminum layer formed on the surface thereof as above dried is then immersed in an alumina The mixture was placed in a crucible, covered, and annealed at 500°C (heating rate 200°C / hour). The holding time was 2 hours, and the oxygen flow rate was 10 L / min. Then, the temperature was lowered to room temperature for 10 hours. The mixture was cooled for 15 hours or less, and the collected material was designated as Sample 15.
[0385] The preparation conditions for Samples 1 to 15 are shown in Table 1.
[0386] [Table 1]
[0387] [XPS] The surface of Samples 1 to 4 prepared above was subjected to XPS analysis. The element concentrations (atomic %) are shown in Table 2.
[0388] [Table 2]
[0389] The data on magnesium and fluorine extracted from Table 2 are shown in Figure 30(A). In sample 4, which did not contain lithium fluoride or magnesium fluoride, The concentrations of potassium and magnesium were low. Sample 3, which was doped with magnesium chloride but not annealed, also showed a significant increase in the amount of fluorine and magnesium. The concentration of sodium did not increase significantly. This is due to the nature of the surface XPS analysis. ) A particle 100 containing a certain element at a high concentration is placed on a particle 1001 containing no certain element. When 2 is attached, the area containing a large area of elements 100 as shown in Figure 30(B2) This is thought to be because certain elements are more difficult to detect from the detection area 1010 than when the detection area 1010 has a 3. can be.
[0390] In addition, samples were added with lithium fluoride and magnesium fluoride and annealed for 2 hours. 2, the fluorine concentration increased significantly. In sample 1, which was doped with magnesium and annealed for 60 hours, the magnesium concentration also increased significantly. there was.
[0391] Comparing sample 2 and sample 1, when annealing is performed, lithium fluoride ( It was speculated that lithium cobalt oxide (melting point 848°C) melts and distributes in the surface layer of the lithium cobalt oxide particles. When the annealing time is further increased, the presence of molten lithium fluoride causes the formation of magnesium fluoride. The melting point of cobalt (melting point 1263°C) drops, and magnesium fluoride melts and becomes cobalt. It was presumed that the cations were distributed in the surface layer of the lithium oxide particles.
[0392] Next, FIG. 31 shows a region showing the carbon bonding state in the XPS narrow scan analysis. In the unannealed sample 3, the peak of CO3 bond was high. In contrast, The CO3 bonds in sample 2 annealed for 60 hours were reduced, while the CO3 bonds in sample 1 annealed for 60 hours were reduced. The CO3 bonds in the surface layer of lithium cobalt oxide are further decreased by lithium carbonate (Li 2Co3), so annealing will cause an excess of lithium. It is believed that this suppresses the formation of an excellent lithium cobalt oxide.
[0393] [SEM] Next, SEM images of Samples 1 to 4 are shown in FIG. 32. FIG. 32(A1) shows Sample 1. FIG. 32(A2) is an enlarged view of the SEM image of sample 2. FIG. 32(B1) is an SEM image of sample 2. FIG. 32(C1) is a SEM image of Sample 3, and FIG. 32(B2) is an enlarged view of the same. 3(C2) is an enlarged view of the same. Fig. 32(D1) is an SEM image of sample 4, and Fig. 32(D2) ) is an enlarged view.
[0394] Sample 4, which is lithium cobalt oxide that has not been treated, has many irregularities on the surface. In sample 3, lithium fluoride and magnesium fluoride were observed. The adhesion of fine particles was observed.
[0395] In contrast, the surfaces of the annealed samples 2 and 1 are smooth and have no irregularities. Sample 1, which was annealed for a longer period of time, had less unevenness than Sample 2. There was a tendency not to.
[0396] [Preparation of secondary battery] Next, using the samples 1, 2, 4 to 15 prepared above, A coin-type secondary battery of the CR2032 type (diameter 20 mm, height 3.2 mm) was fabricated.
[0397] The positive electrode was made of the positive electrode active material prepared above, acetylene black (AB), and polyvinyl chloride (PFC). PVDF was mixed with the positive electrode active material in the ratio of AB:PVDF=95:3:2 (by weight). The resulting slurry was applied to a current collector.
[0398] Lithium metal was used as the counter electrode.
[0399] The electrolyte used in the electrolytic solution is 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte contains ethylene carbonate (EC) and diethyl carbonate (DEC). C:DEC=3:7 (volume ratio), vinylene carbonate (VC) was mixed at 2 wt%. The following was used.
[0400] The separator was made of polypropylene having a thickness of 25 μm.
[0401] The positive electrode can and the negative electrode can were made of stainless steel (SUS).
[0402] The positive electrode of the secondary battery using sample 7 was pressurized with 210 kN. No pressure was applied to the positive electrode of the next battery.
[0403] [Lattice constant calculated from XRD before charging] Before charging using Sample 1, Sample 4, Sample 5 to Sample 12, and Sample 14 The positive electrode was subjected to powder XRD analysis using CuKα1 radiation. XRD was measured in air. The electrodes were attached to a glass plate to keep them flat. The height of the sample was adjusted to fit the measurement surface required by the instrument.
[0404] The obtained XRD patterns were analyzed using DIFFRAC.EVA (Bruker XRD data analysis software). The background and Kα2 were removed using the analysis software. Signals from agents and binders, as well as sealed containers, etc., are also removed.
[0405] The lattice constants were then calculated using TOPAS. No optimization of the atomic positions was performed. Only the lattice constants were fitted. GOF (good of fitness), estimated The crystallite size, a-axis and c-axis lattice constants are shown in Table 3.
[0406] [Table 3]
[0407] Samples 12 and 14, which contain titanium as an impurity at approximately 5100 ppm wt, , the c axis tended to be larger than the others.
[0408] [XRD after first charge] Secondary batteries using Sample 1, Sample 2, Sample 7 and Sample 9 were charged at 4.6 V. CCCV charging was performed. Specifically, after constant current charging at 0.5C up to 4.6V, the current value was 0. The battery was charged at a constant voltage until the battery reached 0.1 C. Here, 1 C was 137 mA / g. The secondary battery in the charged state was disassembled in a glove box with an argon atmosphere to remove the positive electrode. The electrolyte was removed by washing with MC (dimethyl carbonate). The mixture was sealed in a sealed container and subjected to XRD analysis.
[0409] FIG. 33 shows the results of four secondary batteries using Samples 1, 2, 7 and 9. The XRD pattern of the positive electrode after charging at 0.6 V is shown. For comparison, a pseudospinel crystal structure was used. The crystal structure pattern of H1-3 type is also shown.
[0410] After charging to 4.6 V, Sample 1 and Sample 7 were found to have a pseudospinel crystal structure. In addition, from sample 7, in which a magnesium source and a fluorine source were added to the starting material, However, sample 1, which is a mixture of lithium cobalt oxide, magnesium source, and fluorine source, The sharper the pattern, the higher the crystallinity was inferred.
[0411] On the other hand, sample 2, which was insufficiently annealed, and sample 9, which was not annealed, After charging to 4.6 V, it was found that the sample had an H1-3 type crystal structure. The pattern of sample 2 was clearly broader than that of sample 1, suggesting that the crystallinity was low.
[0412] [XRD after first charge by charging depth] Next, the positive electrode active materials of Sample 1 and Sample 2 were used and charged from 4.5 V to 4.65 V. XRD analysis of the charged state was performed on secondary batteries that were charged at various voltages.
[0413] Figure 34 shows the results of measurements using the positive electrode active material of sample 1 at 4.5 V, 4.525 V, 4.55 V, and 4. XRD patterns of the positive electrode after one CCCV charge at 575V, 4.6V, and 4.65V For comparison, the pseudospinel crystal structure, the H1-3 crystal structure and Li 0.35 Co The crystal structure (space group R-3m, O3) pattern for O2 (charge depth 0.65) is shown. The following shows the results.
[0414] As shown in FIG. 34, the positive electrode active material of Sample 1 exhibited L i 0.35 It was found to have the crystal structure of CoO2(O3).
[0415] Also, when charging at 4.55V, Li 0.35 The crystal structure of CoO2(O3) and pseudospinel Since both peaks of the α-type crystal structure were observed, it is believed that these two crystal structures coexist. was speculated.
[0416] When the battery was charged at 4.575 V, a peak corresponding to a pseudo-spinel crystal structure was observed.
[0417] When the battery was charged at 4.6 V, in addition to the peak of the pseudospinel crystal structure, a slight H The peak of the 1-3 crystal structure was observed, which indicates that these two crystal structures coexist. was speculated.
[0418] When charged at 4.65 V, the peaks of the H1-3 type crystal structure were mainly observed. It was presumed that the crystallinity was reduced because of the sharp peak.
[0419] Thus, in the fully annealed sample 1, the Li0 .35 The phase changes from the CoO2(O3) crystal structure to a pseudo-spinel crystal structure, and the charging voltage is 4 It was found that the pseudo-spinel crystal structure is maintained up to about 0.6V. The change was in the charging voltage of about 4.65V.
[0420] Figure 35 shows the results of the test using the positive electrode active material of sample 2 at 4.5 V, 4.55 V, 4.6 V, or 4. The XRD pattern of the positive electrode after one CCCV charge at 65 V is shown. H1-3 type crystal structure, Li 0.35 The crystal structure of CoO2(O3) The pattern and the pattern of the CoO2(O1) type crystal structure are also shown.
[0421] As can be seen from Figure 35, the positive electrode active material of sample 2 exhibits the same properties as sample 1 when charged at 4.5 V. Li 0.35 It was found to have the crystal structure of CoO2(O3).
[0422] However, when charged at 4.55V, unlike sample 1, Li 0.35 CoO2(O3) Peaks of both the crystal structure and the H1-3 type crystal structure were observed.
[0423] Furthermore, when charged at 4.6 V, the peaks of the H1-3 type crystal structure were predominant, unlike sample 1. was observed.
[0424] When charged at 4.65 V, the H1-3 crystal structure and the CoO2(O1) crystal structure were observed. The peaks of the structure were observed. In addition, the peaks were quite broad, and the crystallinity was greatly reduced. It was speculated that this was the case.
[0425] Thus, in sample 2, which was not annealed sufficiently, the charge voltage increased quickly at around 4.55 V. Also 0.35 The phase changed from the CoO2(O3) crystal structure to the H1-3 type crystal structure.
[0426] As explained in the first embodiment, the H1-3 type crystal structure is a crystal structure in the discharged state, and the CoO2 The layers are greatly shifted and the volume difference is large, so the structure changes to the H1-3 type crystal structure repeatedly. It is believed that the crystal structure will collapse as a result of the repeated application of the material. It is necessary to determine the upper limit of the charging voltage so that the crystal structure does not change to the H1-3 type.
[0427] Therefore, as in sample 2, the phase changes to the H1-3 type crystal structure at a charging voltage of about 4.55 V. The upper limit of the charging voltage for the positive electrode active material is less than 4.55V, for example 4.5V.
[0428] On the other hand, the positive electrode active material such as sample 1 maintains a pseudospinel crystal structure even at a charging voltage of 4.6 V. So, the upper limit of the charging voltage can be set to 4.6V. If the charging voltage can be increased, In this case, the capacity per unit weight of the positive electrode active material can be increased, and a high-capacity secondary battery can be obtained. can.
[0429] [XRD after 10 charge / discharge cycles (discharged state)] Next, the secondary batteries using Sample 1 and Sample 2 were charged and discharged 10 times at a high voltage. Specifically, the charge and discharge cycle is repeated 10 times, with CCCV charging (4.6V) followed by CC discharging (2.5V). After the cycle, the discharged secondary battery was disassembled, the positive electrode was taken out, and an XRD analysis was performed.
[0430] FIG. 36 shows the results of the positive electrode of the secondary batteries using Sample 1 and Sample 2 after 10 charge / discharge cycles. The XRD pattern is shown, along with the pattern of the ideal crystal structure of lithium cobalt oxide for comparison. is also shown.
[0431] The pattern of sample 2, which was insufficiently annealed and took on the H1-3 type crystal structure during high-voltage charging, is The sample is brighter than Sample 1, which is sufficiently annealed and has a pseudospinel crystal structure when charged at a high voltage. It was apparently broad and was presumed to have low crystallinity.
[0432] [XRD after 100 charge / discharge cycles (charged state)] Next, the secondary batteries using Sample 1 and Sample 2 were charged with CCCV (4.45 V). After repeating the charge and discharge cycle 100 times, the battery was charged at 4.6V and then discharged at 2.5V. The secondary battery was disassembled, the positive electrode was taken out, and an XRD analysis was performed.
[0433] Figure 37 shows the results of the high-voltage test of secondary batteries using samples 1 and 2 after 100 charge / discharge cycles. The XRD patterns of the positive electrodes charged at high pressure are shown. For comparison, the pseudospinel crystal structure and The H1-3 crystal structure pattern is also shown.
[0434] As shown in FIG. 37, even after 100 cycles, the positive electrode active material of Sample 1 showed pseudo-saturation. It had a pinel crystal structure. Rietveld analysis revealed that it had a pseudo-spinel crystal structure. The proportion of the H1-3 type crystal structure was 43.6 wt%, and the proportion of the H1-3 type crystal structure was 56.4 wt%.
[0435] On the other hand, almost all of the positive electrode active material of sample 2 had the H1-3 type crystal structure. The peak was quite broad, suggesting that the crystallinity had decreased significantly.
[0436] [Cycle characteristics] Next, sample 1, sample 2, sample 4, sample 5, sample 7, sample 10, The cycle characteristics of the secondary batteries using Samples 12 and 13 were evaluated. The results are shown in Figures 38 and 39. The secondary batteries evaluated here had a positive electrode active material layer with a loading amount of 0.1g / cm2. is 7mg / cm 2 More than 8mg / cm 2 These are as follows:
[0437] Figure 38 shows sample 1, sample 2, sample 4, sample 10, sample 12 and sample For sample 13, charging was performed at 25°C using CCCV (0.5C, 4.6V, final current 0.0 The results are shown for 50 cycles of charging at 1C and discharging at CC (0.5C, 2.5V). 38(A) shows the discharge capacity, and FIG. 38(B) shows the discharge capacity retention rate. The current value per unit weight of the electrode active material was 137 mA / g.
[0438] Sample 1, which has a pseudo-spinel crystal structure after annealing for 60 hours and high-voltage charging, is extremely The discharge capacity retention rate after 50 cycles was 96.1%. .
[0439] On the other hand, sample 4 was not treated, and sample 5 was annealed for 2 hours and then charged with H after high voltage charging. Sample 2, which has the 1-3 type crystal structure, was significantly deteriorated. Discharge capacity after 50 cycles The retention rate was below 60% in all cases.
[0440] Aldrich No. 442704 was used as the pre-synthesized lithium cobalt oxide. However, sample 10, which was mixed with the magnesium source and the fluorine source and then annealed, showed good surface roughness. The discharge capacity retention rate after 50 cycles was 79.8%.
[0441] On the other hand, lithium cobalt oxide containing about 5100 ppm wt of titanium as an impurity was used. For samples 12 and 13, after mixing with the magnesium source and the fluorine source, Even though it was annealed, the deterioration was large. This is because the annealing time was short. The same was true for sample 12 and the longer sample 13.
[0442] FIG. 39 shows the results of 100 cycles at 45° C. for Samples 1, 5, and 7. The measurement results are shown in Fig. 39(A) and (B) respectively. The discharge capacity and the discharge capacity retention rate are shown in Fig. 39(A) and (B). In FIG. 39, 1C is a current value per weight of the positive electrode active material of 160 mA / g. The measurement conditions are as follows: Charge is CCCV (1.0C, 4.55V, final current 0.05C), discharge is CC (1.0C , 3.0V).
[0443] Even when measured at 45°C, Sample 1 showed extremely good cycle characteristics. The discharge capacity retention rate after the test was 93.3%. Sample 5, which was prepared in the same manner as sample 1 except that the annealing time was set to 2 hours, also showed excellent results. The results showed excellent cycle characteristics.
[0444] In addition, a magnesium source and a fluorine source are added to the starting material, which is then baked and annealed. Sample 7, in which the above-mentioned battery was used, also exhibited good cycle characteristics.
[0445] In addition, for Sample 1 and Sample 4, the amounts of the positive electrode active material layers are shown in FIG. 38 and FIG. 39. The results of evaluating the cycle characteristics by changing the electrolyte and charging voltage are shown in Figure 40 and Shown in Figure 41.
[0446] All of the secondary batteries used in the evaluation had a positive electrode active material layer loading of 20 mg / cm 2 That's all. The electrolyte was made of ethylene carbonate (EC) and diethyl carbonate (DEC). ) mixed with EC:DEC=3:7 (volume ratio) and vinylene carbonate The charging voltage was 4.5 V. or 4.6V.
[0447] Figure 40 shows the results of the electrochemical analysis using a mixture of EC and DEC in a volume ratio of 3:7. FIG. 40(A) shows the cycle characteristics of Sample 1 and Sample 4. The charging voltage was set to 4.5 V. FIG. 40(B) shows the cycle characteristics when the charging voltage was 4.6 V.
[0448] In addition, in Figure 41, the electrolyte was EC:DEC = 3:7 (volume ratio) with vinylene carbonate ( The cycle characteristics of Sample 1 and Sample 4, which further contain 2 wt% VC, are shown in Fig. Figure 41(A) shows the case where the charging voltage is 4.5V, and Figure 41(B) shows the case where the charging voltage is 4. This shows the cycle characteristics at 6V.
[0449] As is clear from FIG. 40 and FIG. 41, the amount of the positive electrode active material layer, the electrolyte, and the charging voltage Even when the temperature was changed, Sample 1 exhibited extremely good cycle characteristics.
[0450] From the above analysis results, it was found that the pseudo-spinel crystal structure was formed when the battery was charged at a high voltage of 4.6 V. It has been revealed that the positive electrode active material having the above structure exhibits extremely good cycle characteristics. In order to form a pseudo-spinel crystal structure after high-voltage charging, it is necessary to add magnesium and fluorine. It has become clear that annealing at an appropriate temperature and time is effective. The appropriate annealing time depends on the particle size or composition of the lithium cobalt oxide. was assumed to be different.
[0451] In addition, lithium cobalt oxide, which is a starting material with magnesium and fluorine added and sintered, It may be annealed, but it is recommended to use lithium cobalt oxide with few impurities and magnesium and fluorine. It was found that mixing and annealing the above materials was more effective.
[0452] In addition, a comparison of the lattice constant and cycle characteristics reveals that the c-axis lattice constant is 14.060×10 -10 m The following lithium cobalt oxide is used to mix the magnesium source and the fluorine source and anneal. It was found that this tends to result in a positive electrode active material that exhibits good cycle characteristics. First, the layered rock salt type crystal with little foreign element substitution and spinel type crystal structure Co3O4 A complex oxide having this structure is then prepared, and then a magnesium source and a fluorine source are mixed to produce the magnesium By inserting sodium into the lithium site, it is possible to create a positive electrode active material that exhibits good cycle properties. It was thought that.
[0453] [Rate characteristics] Next, Sample 1, which shows extremely good cycle characteristics as described above, and the magnesium source and The secondary battery using Sample 4, which is a comparative example in which no fluorine source was mixed, was The evaluation results of the characteristics are shown in FIG. 42 and FIG.
[0454] The coin cell for evaluating rate characteristics had a positive electrode active material layer loading of 20.8 mg / cm 2 2 more 1.0mg / cm 2 The coin cell for XRD measurement was prepared in the same manner as described above, except for the following. The upper limit for the first charge is 4.5V or 4.6V, and the following settings are available: CCCV, 0.2C, 4.6V, The cut-off current was 0.05 C. The first discharge was CC, 0.2 C, and the cut-off voltage was 3.0 V. In this case, 1C was defined as a current value per unit weight of the positive electrode active material of 200 mA / g. From the second charge and discharge onwards, only the discharge rate was changed to 0.2C charge / 0.2C discharge, 0.2 C charge / 0.5C discharge, 0.2C charge / 1.0C discharge, 0.2C charge / 2.0C discharge, The measurement temperature was 25°C.
[0455] Fig. 42(A) shows the discharge curves at each rate for sample 1 when the charging voltage was 4.5 V, and Fig. 42( B) shows the discharge curves of sample 1 at each rate when the charging voltage is 4.6 V. ) is the discharge curve at each rate of sample 4 when the charging voltage is 4.5V, and Fig. 43(B) is the charging 4 shows the discharge curves of sample 4 at various rates at a voltage of 4.6V.
[0456] As is clear from FIGS. 42 and 43, the secondary battery using Sample 1 has a higher thermal conductivity than Sample 4. In comparison, it shows good rate characteristics when charged at a high voltage, and this tendency becomes stronger as the rate increases. This was particularly evident.
[0457] In addition, in the secondary battery using sample 1, when discharging at a low rate such as 0.2C, It became clear that there was a characteristic voltage change near the end of the test.
[0458] [Charging curve and dQ / dVvsV curve] Next, Sample 1 according to one embodiment of the present invention was prepared by forming an aluminum-containing layer on the surface of the sample. The charging curve and dQ for the secondary battery using sample 15 annealed at 500°C for 2 hours were The results of comparing the / dV vs V curves are shown.
[0459] Secondary batteries using Sample 1 and Sample 15 were charged at 10 mAh / g up to 4.9 V at 25°C. The charging curves are shown in Figure 44. The solid line is sample 1 and the dashed line is sample 15. Two secondary batteries using each sample were measured.
[0460] The dQ / dV vs V curve, which shows the change in voltage relative to the charge capacity, was obtained from the data in Figure 44. The results are shown in Fig. 45. Fig. 45(A) shows the d for sample 1, and Fig. 45(B) shows the d for sample 15. This is the Q / dV vs V curve.
[0461] As is clear from Fig. 45(A) and Fig. 45(B), either Sample 1 or Sample 15 Even in this case, peaks were observed at voltages of approximately 4.06 V and 4.18 V. The change in capacity was nonlinear with the charge depth of 0.5. The space group P2 / m at a charge depth of 0.5 is shown in Figure 1. As shown in Figure 4, the lithium atoms are aligned. Energy is used to align the lithium atoms. It is believed that this causes the change in capacitance to become nonlinear with respect to voltage.
[0462] In addition, in the comparative sample 15, a large peak was observed at approximately 4.54V and 4.61V. Between these two peaks is the H1-3 phase type crystal structure. .
[0463] On the other hand, sample 1, which shows extremely good cycle characteristics, has a small peak at about 4.55 V. However, it was not clear. Therefore, dQ / d was obtained from more detailed measurement results. The VvsV curves are shown in Figures 46 and 47. Figure 47 is an expanded view of Figure 46.
[0464] As shown in Figure 47, detailed measurements reveal that the peaks are at approximately 4.55V and 4.63V. The area between these two peaks is considered to be a pseudo-spinel crystal structure. The region between the peaks at about 4.63 V and 4.64 V is considered to be an H1-3 type crystal structure. can be done.
[0465] As shown in the dQ / dV vs V curve of sample 1, some peaks are very broad and In such cases, two crystal structures may coexist. For example, two phases of O3 and pseudospinel coexist, or two phases of pseudospinel and H1-3 coexist. It is possible that.
[0466] [Discharge curve and dQ / dVvsV curve] Next, a secondary battery using Sample 1, which is one embodiment of the present invention, and Sample 4, which is a comparative example, was The results of comparing the discharge curve and the dQ / dV vs V curve are shown below.
[0467] FIG. 48(A) shows the discharge curve of Sample 1, and FIG. 48(B) shows the discharge curve of Sample 4. In both cases, the battery was discharged after CCCV charging at 4.6V. The discharge was CC discharge down to 2.5V. The discharge rate was 0.05C (1C = 200mA / g).
[0468] As shown in FIG. 48(A), in sample 1, near the end of discharge (area surrounded by dashed line in the figure), A characteristic voltage change was observed. This is the same as that observed in the low-rate discharge in Figure 40. It is the same as change.
[0469] The dQ / dV vs V curve, which shows the change in voltage relative to the discharge capacity, was obtained from the data in Figure 48. The dQ / dVv of sample 1 is shown in FIG. 49(A), and the dQ / dVv of sample 4 is shown in FIG. 49(B). This is the sV curve. In order to clearly depict the peak, the graph is for the voltage range above 3.5V.
[0470] As shown in FIG. 49(B), Sample 4, which does not contain a magnesium source and a fluorine source, In the case of the 100V- ... It became clear that the discharge curve of sample 4 had two inflection points.
[0471] On the other hand, as is clear from FIG. 49(A), Sample 1 has many more downward convex peaks. The largest peak was observed at about 3.9 V. Also, as indicated by the arrow in the figure, As shown in the figure, at least one peak was present in the range of 3.5 V to 3.9 V. The peak indicates the change in voltage in the area surrounded by the dashed line in FIG.
[0472] As described above with reference to Figs. 40, 48 and 49, the sample according to one embodiment of the present invention The positive electrode active material of Pulse 1 is charged at a high voltage and then discharged at a low rate, for example, 0.2 C or less. It was found that a characteristic voltage change appears near the end of discharge. At least one peak in the dQ / dV vs V curve between 3.5V and 3.9V This can be clearly seen by the existence of EXAMPLES
[0473] In this example, a positive electrode active material containing cobalt and nickel as transition metals was prepared. Characteristics were analyzed using RD.
[0474] [Preparation of positive electrode active material] <Sample 21> As sample 21, a cobalt and nickel source was prepared by the method shown in FIG. 1 of the first embodiment. The ratio of the number of nickel atoms (Ni) to the total number of atoms (Co+Ni) ) was prepared as a positive electrode active material having a molecular weight of 0.01.
[0475] First, similarly to steps S11 to S14 of the first embodiment and the first example, LiF A first mixture was prepared in which the molar ratio of LiF to MgF2 was 1:3.
[0476] Next, as in steps S21 and S22 of the first embodiment, Li:Ni:Co The atomic ratio of Ni / (Co+Ni) was 1:0.01:0.99 (Ni / (Co+Ni)=0.01). The materials were weighed and mixed. The lithium source was lithium carbonate, and the cobalt source was cobalt oxide. The nickel source was nickel hydroxide. Setone was added and the mixture was wet mixed.
[0477] Next, as in steps S23 to S25 of the first embodiment, the mixture is mixed in a dry air atmosphere. After baking in a blast furnace at 900°C for 10 hours, the material was collected and the lithium, cobalt, nickel and A composite oxide containing oxygen and oxygen was obtained. The flow rate of the dry air was 10 L / min. The temperature was raised by 20 The temperature was decreased to 0°C / hr over a period of 10 hours or more.
[0478] Next, the first mixture and lithium are mixed as in steps S31 to S33 of the first embodiment. A complex oxide having aluminum, cobalt, nickel and oxygen is mixed to prepare a second mixture. The number of magnesium atoms in the first mixture was calculated based on the sum of the number of cobalt and nickel atoms. The atomic weight of the ruthenium was 0.5 atomic %.
[0479] Next, as in steps S34 and S35 of the first embodiment, the second mixture is The cathode active material was obtained after annealing in a muffle furnace in an oxygen atmosphere at 850°C for 2 hours and then recovering the material. The oxygen flow rate was 10 L / min. The temperature rise rate was 200°C / hr, and the temperature drop rate was 10 hours or more. The positive electrode active material thus obtained was designated as Sample 21.
[0480] <Sample 22> In step S11, LiF and MgF2 are not added, and in step S34, The positive electrode active material was prepared in the same manner as Sample 21 except that annealing was not performed. This was designated as a comparative example.
[0481] <<Sample 23>> In step S21, the raw materials were weighed so that Ni / (Co+Ni)=0.075. A positive electrode active material prepared in the same manner as Sample 21 was used as Sample 23.
[0482] <<Sample 24>> In step S11, LiF and MgF2 are not added, and in step S34, The positive electrode active material was prepared in the same manner as Sample 23 except that annealing was not performed. This was designated as a comparative example.
[0483] <Sample 25> In step S21, the raw materials were weighed so that Ni / (Co+Ni)=0.1. A positive electrode active material prepared in the same manner as Sample 21 was used as Sample 25.
[0484] <Sample 26> In step S11, LiF and MgF2 are not added, and in step S34, The positive electrode active material was prepared in the same manner as Sample 25 except that annealing was not performed. This was designated as a comparative example.
[0485] The preparation conditions for Samples 21 to 26 are shown in Table 4.
[0486] [Table 4]
[0487] [Preparation of secondary battery] Next, using the samples 21 to 26 prepared above, coins were A secondary battery of this type was fabricated.
[0488] [XRD after first charge] The secondary batteries using Samples 21 to 26 were subjected to CC charging at 4.6 V in the same manner as in Example 1. After CV charging, the positive electrode was taken out and subjected to XRD analysis.
[0489] Figures 50 and 51 show the results of the secondary batteries using Sample 21 and Sample 22 at 4.6 V. The XRD pattern of the positive electrode after charging is shown in FIG. 51(A). The part of 2θ=20° is shown in enlargement. Figure 51(B) shows the part of 2θ=43° in Figure 50. The area at 2θ=46° is shown in enlarged view. For comparison, the pseudo-spinel crystal structure, H1- Type 3 crystal structure and Li 0.35 The crystal structure pattern of CoO2 (charge depth 0.65) The pseudo-spinel type crystal structure, H1-3 type crystal structure, and Call Li 0.35 The comparison patterns of the crystal structure of CoO2 are all transition metals. The calculations were performed for a structure that had only nickel and no nickel.
[0490] In sample 21, which was added with Mg and F sources and annealed, the pseudo-spinel crystal structure was formed. The peak was observed. In addition, the H1-3 type crystal structure and Li 0.35 CoO2 crystals The peaks of the structure were also observed. Also, some peaks were shifted from the comparative pattern. , thought to be due to the influence of nickel.
[0491] On the other hand, in sample 22, which was not added with Mg or F sources and was not annealed, pseudo-spinel No peaks of the H1-3 type crystal structure were observed. However, the H1-3 type crystal structure and Li 0.35 The peak of the crystal structure of CoO2 was observed.
[0492] FIG. 52 shows the results after charging the secondary batteries using Samples 23 and 24 at 4.6 V. The XRD pattern of the positive electrode is shown. For comparison, the pseudo-spinel crystal structure and the H1-3 crystal structure are shown. and Li 0.35 The crystal structure pattern for CoO2 (charge depth 0.65) is also shown. Shown below.
[0493] In sample 23, which was added with Mg and F sources and annealed, a pseudo-spinel crystal structure and Although peaks of the H1-3 crystal structure were observed, the peaks of the pseudospinel crystal structure were dominant. It was.
[0494] On the other hand, in sample 24, which was not added with Mg or F sources and was not annealed, the H1-3 type Crystal structure and Li 0.35 The peak of the crystal structure of CoO2 was observed. It was presumed that the crystallinity was reduced because of the large distortion and broad peaks.
[0495] FIG. 53 shows the results after charging the secondary batteries using Samples 25 and 26 at 4.6 V. The XRD pattern of the positive electrode is shown. For comparison, the pseudo-spinel crystal structure and the H1-3 crystal structure are shown. and Li 0.35 The crystal structure pattern for CoO2 (charge depth 0.65) is also shown. Shown below.
[0496] In samples 25 and 26, where Ni / (Co+Ni) was 0.1, the crystal structure No significant difference was observed. In addition, this crystal structure is similar to the pseudospinel crystal structure, H1-3 Crystal structure and Li 0.35 It was speculated that it was neither CoO2 nor any of the above.
[0497] 50 to 53, the positive electrode active material having lithium, a transition metal, and oxygen has the following main components: When the transition metals are cobalt and nickel, Ni / (Co+Ni) is less than 0.1. It has become clear that the Ni / ( When the content of Co+Ni is within the above range, the Mg source and F source are added and annealed. This is because the material has a pseudo-spinel crystal structure at a charged voltage of 4.6 V. As described in the previous examples, the positive electrode active material having a pseudo-spinel crystal structure in this embodiment has good It exhibits good cycle characteristics. EXAMPLES
[0498] In this example, a secondary battery using a positive electrode active material according to one embodiment of the present invention was manufactured, and a differential scanning calorimeter was Differential scanning calorimetry (DS C) and a charging endurance test were performed.
[0499] <Sample 27> The lithium phosphate was ground in a mortar made of zirconia.
[0500] The lithium phosphate that was crushed in a mortar was mixed with the sample 1 prepared in the previous example. The amount of lithium phosphate mixed was equivalent to 0.04 mol per 1 mol of sample 1. The mixing was carried out in a ball mill using zirconia balls at 150 rpm and 1 After mixing, the mixture was sieved through a 300 μm φ sieve. The mixture was placed in a Na crucible, covered, and annealed in an oxygen atmosphere at 850°C for 2 hours. After sieving through a 3 μm diameter sieve, sample 27 was obtained.
[0501] <<Sample 28>> Lithium phosphate was crushed. The crushing was carried out in a ball mill using zirconia balls. The mixture was ground at 100 rpm for 60 hours, and then sieved through a 300 μm φ sieve.
[0502] Pulverized lithium phosphate was mixed with Sample 1 prepared in the previous example. The amount of lithium phosphate combined was equivalent to 0.06 mol per 1 mol of sample 1. The mixture was mixed in a ball mill using zirconia balls at 150 rpm for 1 hour. After mixing, the mixture was sieved through a 300 μm φ sieve. The resulting mixture was then sieved in an alumina crucible. The mixture was placed in a pot, covered, and annealed in an oxygen atmosphere at 750°C for 20 hours. The mixture was sieved through a 1 μm diameter sieve to obtain sample 28.
[0503] [Preparation of secondary battery] Next, Samples 27 and 28 prepared above and Sample 1 shown in the previous example were A CR2032 type coin-type secondary battery was fabricated using the above.
[0504] For the positive electrode, sample 1, sample 27, or sample 28 was used as the active material. A slurry of active material, AB, and PVDF mixed at a ratio of 95:3:2 (weight ratio) The current collector was coated with the above-mentioned material.
[0505] Lithium metal was used as the counter electrode.
[0506] The electrolyte used in the electrolytic solution is 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte used in the secondary batteries for which the charge / discharge characteristics were evaluated was ethylene carbonate (E C) and diethyl carbonate (DEC) were mixed in a volume ratio of EC:DEC = 3:7. The secondary batteries for which the cycle characteristics were evaluated (described later) were made of ethylene carbonate (EC) and Diethyl carbonate (DEC) is EC:DEC=3:7 (volume ratio), vinylene carbonate is The composite was mixed with 2 wt% VC.
[0507] The separator was made of polypropylene having a thickness of 25 μm.
[0508] The positive electrode can and the negative electrode can were made of stainless steel (SUS).
[0509] The positive electrode of the secondary battery was pressurized with 210 kN / m, and then further pressurized with 1467 kN / m. The amount of support on the positive electrode using Sample 1 was approximately 21 mg / cm 2 The electrode density is approximately 3.9g / cm 3 The amount of support on the positive electrode using sample 28 was approximately 20 mg / cm. m 2 , electrode density is approximately 3.7g / cm 3 It was.
[0510] [Charge / discharge characteristics] The secondary batteries using Sample 1 and Sample 28 were charged with CCCV (0.05C, 4. 5V or 4.6V, final current 0.005C), discharge at CC (0.5C, 2.5V) The initial charge capacity, discharge capacity, and coulombic efficiency are shown in Table 5. What is coulombic efficiency? The discharge capacity is normalized by the charge capacity and expressed as a percentage. Ron efficiency was obtained.
[0511] [Table 5]
[0512] [Cycle characteristics] The secondary batteries using Sample 1 and Sample 28 were charged with CCCV (0.05C, 4. 5V or 4.6V, final current 0.005C), discharge to CC (0.05C, 2.5V) The measurement was performed for two cycles at 25°C.
[0513] Thereafter, the secondary batteries using Sample 1 and Sample 28 were charged at 25°C. CCV (0.2C, 4.5V or 4.6V, final current 0.02C), discharge CC (0. The battery was repeatedly charged and discharged at 2C and 2.5V to evaluate the cycle characteristics. The capacity retention rate of sample 1 was 99.0% at a charging voltage of 4.5 V and 99.0% at a charging voltage of 4.6 V. For sample 28, the charge voltage was 4.5 V and the charge voltage was 4.5 V. For sample 30, the charge voltage was 4.5 V and the charge voltage was 4.5 V. The capacity retention rate after 50 cycles was 97.8% at a voltage of 4.6 V. The charge voltage was 4.5V and the charge rate was 97.3%, 4.6V and 80.0%, respectively. In sample 28, the charge rate was 96.6% at a charging voltage of 4.5V and 93.5% at a charging voltage of 4.6V. 5.5%. Figure 54(A) shows the change in discharge capacity at a charging voltage of 4.5 V. 4(B) shows the change in discharge capacity for a charging voltage of 4.6 V. The horizontal axis of each graph shows the number of cycles, and the vertical axis shows the discharge capacity. In the case of the battery 28, the charge / discharge capacity is reduced by the weight of the lithium phosphate, but the cycle characteristics are improved. This is because the lithium phosphate coating prevents metals such as cobalt from being absorbed from the positive electrode active material. This is thought to be the result of suppressing the dissolution of ions and inhibiting decomposition of the electrolyte.
[0514] [Differential scanning calorimetry] The secondary batteries using Sample 1, Sample 27 and Sample 28 were charged with CCCV (0 .05C, 4.5V or 4.6V, final current 0.005C), discharge to CC(0.05C , 2.5 V) at 25° C. for two cycles.
[0515] After that, the secondary batteries using Sample 1, Sample 27, and Sample 28 were charged with CC CV (0.05C, 4.5V or 4.6V, final current 0.005C) was performed. The charged secondary battery was disassembled in a glove box with an argon atmosphere and the positive electrode was removed. The electrolyte was removed by washing with DMC, and then punched out to a diameter of 3 mm.
[0516] 1 μL of electrolyte was dropped onto the punched positive electrode and placed in a SUS sealed container. The electrolyte used was 1 mol / L lithium hexafluorophosphate (LiPF6), and the electrolyte solution was , ethylene carbonate (EC) and diethyl carbonate (DEC) have an EC:DEC=3 A mixture of these materials at a volume ratio of 1:7 was used.
[0517] Evaluation was performed using DSC. The measurement was performed using a Rigaku high-sensitivity differential scanning calorimeter, Thermo p The lus EV02 DSC8231 was used. The measurement conditions were room temperature to 400°C. The temperature rise rate was set to 5°C / min.
[0518] The results of the DSC measurement are shown in Figure 55. The horizontal axis shows temperature and the vertical axis shows Heat flow is shown in Fig. 55(A) for comparison of sample 1 and sample 27. FIG. 55(B) shows a comparison of Sample 1 and Sample 28, respectively.
[0519] As shown in FIG. 55(A), peaks were observed near 171°C and 251°C in sample 1. In sample 27, the temperature rose to around 188°C and 252°C, respectively, and the The area intensity, which indicates the amount of heat, decreased. Also, as shown in FIG. 55(B), the peak An increase in cracks and a decrease in area strength were observed, especially in the range of 150°C to 200°C. A significant decrease in the area intensity was observed. From the above, it was found that phosphoric acid was used in the preparation process of the positive electrode active material. It was suggested that mixing with a compound that has a similar effect on thermal stability could improve thermal stability.
[0520] [Charging endurance test] The secondary batteries using Sample 1 and Sample 28 were charged with CCCV (0.05C, 4. 5V or 4.6V, final current 0.005C), discharge to CC (0.05C, 2.5V) The measurement was performed for two cycles at 25°C.
[0521] After that, the battery was charged at 60°C with CCCV (0.05C). The upper limit voltage was 4.55V. or 4.65V, and the termination condition is when the secondary battery voltage is 0.01V below the upper limit voltage ( The time until the voltage of the secondary battery dropped below 4.55V was measured. If the voltage falls below the upper limit voltage, a phenomenon such as a short circuit may have occurred. 1C was set to 200mA / g.
[0522] The times measured for each secondary battery are shown in Table 6.
[0523] [Table 6]
[0524] In sample 28, it took a long time for the voltage of the secondary battery to decrease, and the positive electrode active material was It was suggested that mixing the compound with phosphoric acid in the electrolyte improves charging durability. EXAMPLES
[0525] In this example, a secondary battery using the positive electrode active material of one embodiment of the present invention was manufactured, and the battery was subjected to atomic absorption spectrometry. Metal elution was evaluated by measurement.
[0526] [Preparation of secondary battery] First, the above-prepared sample 27 and the sample 1 shown in the previous example were used to perform lamination. A laminate-type secondary battery was fabricated.
[0527] For the positive electrode, sample 1 or sample 27 was used as the active material, and the mixture of AB and PVDF was used. The slurry was mixed with the active material, AB, and PVDF in a ratio of 95:3:2 (by weight) and applied to one side of the current collector. The material used was coated with
[0528] The negative electrode uses graphite as the active material, and is made of VGCF (registered trademark), CMC-Na, and SBR. The composition of the active material was: VGCF (registered trademark): CMC-Na: SBR = 96: 1: 1: 2 (by weight) The slurry was mixed in the ratio of 1:1 and the viscosity was adjusted with pure water. The slurry was then applied to one side of the current collector, dried, and then pure water was added. The volatilized material was used. A copper foil with a thickness of 18 μm was used as the current collector. The amount of support was approximately 14 mg / cm 2 It was.
[0529] The electrolyte used in the electrolytic solution is 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte contains ethylene carbonate (EC) and diethyl carbonate (DEC). C:DEC=3:7 (volume ratio), vinylene carbonate (VC) was mixed at 2 wt%. The following was used.
[0530] The separator was made of polypropylene having a thickness of 25 μm.
[0531] The secondary battery produced was subjected to a process of degassing by charging and discharging at a low rate for the purpose of aging. I went there a few times.
[0532] A positive electrode having Sample 1 or Sample 27 and a negative electrode having graphite were combined to produce a After aging the secondary battery, charge it at CCCV (0.05C, 4.4 The discharge was performed at CC (0.05C, 2.5V, final current 0.005C). It was set at approximately 200 mA / g.
[0533] Then, charging was performed using CCCV (0.05C, 4.45V, final current 0.005C). Thereafter, the secondary battery was stored at 60° C. for 14 days.
[0534] Then, the battery was discharged at CC (0.05C, 2.5V) at 25°C. It was expressed as mA / g.
[0535] [Atomic absorption measurement] Next, the secondary battery was disassembled in an argon atmosphere glove box to remove the negative electrode, and the DM The electrolyte was removed by washing with 0.2% NaCl. The current collector was then removed. The powder of the active material layer was mixed. Approximately 0.1 mg was then taken out and subjected to atomic absorption spectrometry.
[0536] The amount of cobalt was measured using furnace atomic absorption spectrometry. ContrAA 600 Continuum Source Atomic Absorption Spectroscopy by Analytik Jena In the measurement, cobalt was atomized at 2500°C and the wavelength was 235.8183 nm. Two secondary batteries were fabricated for each of Sample 1 and Sample 27. The measurement was performed 20 times for each cell, and the average value was calculated.
[0537] The amount of cobalt obtained was 9722 ppm for sample 1 and 597 ppm for sample 27. The amount of cobalt was normalized based on the amount of cobalt in the positive electrode active material layer. Specifically, the amount of cobalt contained in the entire negative electrode of the secondary battery is calculated from the obtained measured values. The amount of cobalt in the positive electrode of the secondary battery was used as the standard. The amount of balt was reduced. During the process of preparing the positive electrode active material, the compound containing phosphoric acid was mixed with This suppressed the elution of cobalt from the positive electrode active material and reduced the amount of cobalt deposited on the negative electrode. It is suggested that... EXAMPLES
[0538] In this example, a positive electrode active material according to one embodiment of the present invention was prepared and its characteristics were analyzed by XRD. In addition, the cycle characteristics during high-voltage charging were evaluated.
[0539] <Sample 51> The same procedure was carried out as in Example 1 except that the annealing time in step S34 of FIG. Sample 51 was prepared in the same manner as in Sample 1.
[0540] <Sample 52> The same procedure as in Example 1 was repeated except that the annealing time in step S34 of FIG. Sample 52 was prepared in the same manner as Sample 1.
[0541] [XRD after first charge] In the same manner as in Example 1, a secondary battery was produced using Sample 51 and Sample 52, and the initial charge A charge was performed and the XRD was evaluated after the first charge.
[0542] FIG. 56 shows the positive and negative charge of the secondary batteries using Sample 51 and Sample 52 after charging at 4.6 V. The XRD patterns of the poles are shown.
[0543] After charging to 4.6 V, it was revealed that Sample 52 had a pseudospinel crystal structure. On the other hand, sample 51 suggested an H1-3 type crystal structure. It is suggested that a better positive electrode active material can be obtained with a heating time of 30 hours than with a heating time of 8 hours. It was suggested that the annealing time should be longer than 8 hours.
[0544] [Cycle characteristics] As in Example 1, the secondary batteries using Samples 51 and 52 were cycled. The characteristics were evaluated.
[0545] At 25°C, charging is CCCV (1C, 4.6V, final current 0.01C), discharging is CC (0. The cycle characteristics were evaluated at 1 C and 2.5 V. The discharge capacity retention rate after 40 charge / discharge cycles was 47.8 for sample 28. %, Sample 29 was 98.4%, and Sample 1 prepared in Example 1 was 97.6%. Ta.
[0546] At 45°C, charging is CCCV (1C, 4.55V, final current 0.05C), discharging is CC (1 The cycle characteristics were evaluated at 1 C and 3.0 V. 1 C was approximately 160 mA / g. The discharge capacity retention rate after 100 charge / discharge cycles was 39. 4%, and in sample 52 it was 78.4%.
[0547] Sample 52 showed excellent cycle characteristics at both 25°C and 45°C. This shows that an excellent positive electrode active material can be obtained by annealing for 30 hours. I was tempted. EXAMPLES
[0548] In this example, a positive electrode active material according to one embodiment of the present invention was prepared and its characteristics were analyzed by XRD. In addition, the cycle characteristics during high-voltage charging were evaluated.
[0549] <Sample 61> In step S11 of FIG. 2, MgF2 was not added, and the other conditions were the same as those in Example 1. Sample 61 was prepared in the same manner as Sample 1. Molecular weight of lithium cobalt oxide The first mixture was weighed out so that the atomic weight of lithium in the first mixture was 1.17 atomic %. Dry mixed.
[0550] <Sample 62> In step S11 of FIG. 2, LiF and MgF2 are not added, but instead Mg(OH) The other conditions were the same as those for Sample 1 in Example 1. The molecular weight of the lithium cobalt oxide was 62. The atomic weight of aluminum was weighed out to be 0.5 atomic % and mixed in a dry state.
[0551] [XRD after first charge] In the same manner as in Example 1, a secondary battery was produced using Sample 61 and Sample 62, and the initial charge A charge was performed and the XRD was evaluated after the first charge.
[0552] Figure 57 shows the positive and negative polarities of the secondary batteries using Sample 61 and Sample 62 after charging at 4.6 V. The XRD patterns of the poles are shown.
[0553] After charging to 4.6 V, both sample 61 and sample 62 have a H1- rather than a pseudo-spinel crystal structure. The result suggests that the crystal structure is type 3. In the case of using a compound having lithium and a compound having fluorine, a better positive It was suggested that a positive electrode active material could be obtained.
[0554] [Cycle characteristics] As in Example 1, the secondary batteries using Samples 61 and 62 were cycled. The characteristics of the battery were evaluated. Figure 58(A) shows the results of cycle measurements at 25°C and a charging voltage of 4.6V. Figure 58(B) shows the results of charging at 45°C and a charging voltage of 4.55V. Both Sample 61 and Sample 62 were cycle-reduced compared to Sample 1 shown in Example 1. The decrease in capacity due to the high voltage charging was more pronounced. This is probably because it was not measured. [Explanation of symbols]
[0555] 100 Cathode active material 1001 particles 1002 Fine particles 1003 area 1010 Detection area
Claims
1. A lithium ion secondary battery having a positive electrode and a negative electrode, The positive electrode comprises a positive electrode active material having lithium, cobalt, magnesium, and oxygen; The positive electrode active material has a surface portion and an interior portion, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior portion, The positive electrode active material is A lithium ion secondary battery in which a coin cell having the positive electrode and lithium metal as a counter electrode is charged to a charge capacity of 219.2 mAh / g or more, and then the positive electrode is removed from the coin cell in an argon atmosphere and subjected to powder XRD analysis using CuKα1 radiation, the result being diffraction peaks at least at 2θ=19.30±0.20° and 2θ=45.55±0.10°.
2. A lithium ion secondary battery having a positive electrode and a negative electrode, The positive electrode comprises a positive electrode active material having lithium, cobalt, magnesium, and oxygen; The positive electrode active material has a surface portion and an interior portion, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior portion, The positive electrode active material is A lithium ion secondary battery in which a coin cell having the positive electrode and lithium metal as a counter electrode is charged to a charge capacity of 231 mAh / g, and then the positive electrode is removed from the coin cell in an argon atmosphere and subjected to powder XRD analysis using CuKα1 radiation, the resultant battery having diffraction peaks at least at 2θ=19.30±0.20° and 2θ=45.55±0.10°.
3. A lithium ion secondary battery having a positive electrode and a negative electrode, The positive electrode comprises a positive electrode active material having magnesium and lithium cobalt oxide; The positive electrode active material has a surface portion and an interior portion, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior portion, The positive electrode active material is A lithium ion secondary battery in which a coin cell having the positive electrode and lithium metal as a counter electrode is charged to a charge capacity of 219.2 mAh / g or more, and then the positive electrode is removed from the coin cell in an argon atmosphere and subjected to powder XRD analysis using CuKα1 radiation, the result being diffraction peaks at least at 2θ=19.30±0.20° and 2θ=45.55±0.10°.
4. A lithium ion secondary battery having a positive electrode and a negative electrode, The positive electrode comprises a positive electrode active material having magnesium and lithium cobalt oxide; The positive electrode active material has a surface portion and an interior portion, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior portion, The positive electrode active material is A lithium ion secondary battery in which a coin cell having the positive electrode and lithium metal as a counter electrode is charged to a charge capacity of 231 mAh / g, and then the positive electrode is removed from the coin cell in an argon atmosphere and subjected to powder XRD analysis using CuKα1 radiation, the resultant battery having diffraction peaks at least at 2θ=19.30±0.20° and 2θ=45.55±0.10°.
5. A lithium ion secondary battery having a positive electrode and a negative electrode, The positive electrode comprises a positive electrode active material having lithium, cobalt, magnesium, and oxygen; The positive electrode active material has a surface portion and an interior portion, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior portion, The positive electrode active material is A lithium ion secondary battery having a space group of R-3m and a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0, 0, 0.5) and the coordinates of oxygen are represented by (0, 0, x) (where 0.20≦x≦0.25) when a coin cell having lithium metal as the positive electrode and a counter electrode is charged to a charge capacity of 219.2 mAh / g or more.
6. A lithium ion secondary battery having a positive electrode and a negative electrode, The positive electrode comprises a positive electrode active material having lithium, cobalt, magnesium, and oxygen; The positive electrode active material has a surface portion and an interior portion, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior portion, The positive electrode active material is A lithium ion secondary battery having a space group of R-3m and a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0, 0, 0.5) and the coordinates of oxygen are represented by (0, 0, x) (where 0.20≦x≦0.25) when a coin cell having lithium metal as the positive electrode and a counter electrode is charged to a charge capacity of 231 mAh / g.
7. A lithium ion secondary battery having a positive electrode and a negative electrode, The positive electrode comprises a positive electrode active material having magnesium and lithium cobalt oxide; The positive electrode active material has a surface portion and an interior portion, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior portion, The positive electrode active material is A lithium ion secondary battery having a space group of R-3m and a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0, 0, 0.5) and the coordinates of oxygen are represented by (0, 0, x) (where 0.20≦x≦0.25) when a coin cell having lithium metal as the positive electrode and a counter electrode is charged to a charge capacity of 219.2 mAh / g or more.
8. A lithium ion secondary battery having a positive electrode and a negative electrode, The positive electrode comprises a positive electrode active material having magnesium and lithium cobalt oxide; The positive electrode active material has a surface portion and an interior portion, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior portion, The positive electrode active material is A lithium ion secondary battery having a space group of R-3m and a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0, 0, 0.5) and the coordinates of oxygen are represented by (0, 0, x) (where 0.20≦x≦0.25) when a coin cell having lithium metal as the positive electrode and a counter electrode is charged to a charge capacity of 231 mAh / g.
9. In any one of claims 1 to 8, The inside of the positive electrode active material contains aluminum, The inside of the positive electrode active material has a layered rock salt type crystal structure.
10. In any one of claims 1 to 9, The surface layer portion of the positive electrode active material contains fluorine, At least a portion of a surface layer of the positive electrode active material has a rock salt crystal structure.
11. In any one of claims 1 to 10, A lithium ion secondary battery, wherein a surface layer portion of the positive electrode active material contains cobalt.
12. In any one of claims 1 to 4, a ratio of a crystal structure having the diffraction peak to 50 wt % or more when the diffraction peak is subjected to Rietveld analysis;
13. In any one of claims 5 to 8, The proportion of the crystal structure is 50 wt % or more, The ratio is determined by Rietveld analysis.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery and method for manufacturing the same
JP2002216760A
Positive electrode material for lithium secondary battery
JP2006164758A
Positive electrode active material for lithium secondary battery and its manufacturing method
JP2006261132A